Injection molded products, optical parts, or automotive parts

By introducing ring structural units into methacrylic resin and controlling their molecular weight distribution, the problem of birefringence during injection molding is solved, and imaging performance and thermal stability are improved in high-temperature environments are achieved. It is suitable for injection molding products with complex shapes and thin-wall structures.

JP7628163B2Active Publication Date: 2025-02-07ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023188695
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-07-13
Filing Date
2023-11-02
Publication Date
2025-02-07
Estimated Expiration
2039-07-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the birefringence phenomenon of plastics during injection molding, especially in electronic equipment and automotive parts used in high temperature environments, resulting in a degradation of imaging performance.

Method used

A methacrylic resin containing ring structural units is used to control the molecular weight distribution of the resin and the proportion of ring structural units, and adjust its composition in different molecular weight regions to ensure the difference in birefringence phenomena under different degrees of orientation and reduce the birefringence effect of injection molded products.

Benefits of technology

It realizes effective control of birefringence phenomena in high temperature environments, improves imaging performance and thermal stability, and is suitable for injection molding products with complex shapes and thin-walled structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628163000012
    Figure 0007628163000012
  • Figure 0007628163000001
    Figure 0007628163000001
  • Figure 0007628163000002
    Figure 0007628163000002
Patent Text Reader

Abstract

To provide a methacrylic resin having high heat resistance and highly controlled birefringence and suitable for injection molding application, a methacrylic resin molded body comprising the methacrylic resin, and an optical component or an automobile component formed of the methacrylic resin molded body.SOLUTION: An injection molded body having a fine concavo-convex pattern formed on the surface thereof is obtained by use of a composition comprising a methacrylic resin that contains a structural unit having a ring structure in the main chain. The fine concavo-convex pattern has a height or a recess of 0.1 to 500 μm and a pitch distance in the concavo-convex pattern of 10 to 1000 μm, and the methacrylic resin has a glass transition temperature of over 120°C and 160°C or lower. A difference in abundance of the structural unit having a ring structure in the main chain between a fraction component having a peak top molecular weight of 40,000 to 50,000 and a fraction component having a peak top molecular weight of 240,000 to 260,000, both obtained by molecular weight fractionation, is 3.0 mass% or less. An optical component or an automobile component is also disclosed.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an injection-molded article obtained from a methacrylic resin which has high heat resistance and highly controlled birefringence and is suitable for injection molding, and to an optical part or automobile part obtained from the injection-molded article. [Background technology]

[0002] Traditionally, glass was used for optical components such as lenses and prisms, but in recent years, plastics have come to be used due to the need for greater design freedom, such as for lightweight and compact lenses and aspheric lenses. Generally, methacrylic resins, styrene resins, polycarbonates, and cyclic olefin resins are known plastics used for optical components.

[0003] In general, plastics are prone to birefringence due to orientation during molding, which adversely affects imaging performance when used as optical components. Furthermore, when injection molding, which has high productivity, is used as a molding method, larger orientation is likely to occur, and the impact on imaging performance becomes more pronounced. Methacrylic resins, such as polymethyl methacrylate, have been used favorably as optical components because of their small intrinsic birefringence and relatively small orientation birefringence. However, as higher optical performance is now required, materials that can reduce orientation birefringence are in demand.

[0004] For example, Patent Documents 1 and 2 disclose that the orientation birefringence and photoelastic birefringence can be reduced by a copolymer obtained by copolymerizing monomers including methyl methacrylate, 2,2,2-trifluoroethyl methacrylate, and benzyl methacrylate. This is based on the idea of ​​selecting multiple monomers with different signs of intrinsic birefringence and photoelastic coefficient when made into homopolymers, combining and copolymerizing them to adjust the composition, thereby reducing the orientation birefringence and photoelastic birefringence of the copolymer. However, this copolymer has a low glass transition temperature, so there is a problem that its use is limited inside electronic devices and automobiles, where the insides can become hot.

[0005] For this reason, as resins for injection molding with improved orientation birefringence and heat resistance, a copolymer obtained by hydrogenating aromatic double bonds of a copolymer obtained by polymerizing a monomer composition containing a (meth)acrylic acid ester monomer and an aromatic vinyl monomer (Patent Document 3) and a (meth)acrylic resin having a glutarimide unit with a ring structure in the main chain (Patent Document 4) have been proposed. However, although the orientation birefringence of these resins is low, the photoelastic coefficient is not sufficiently reduced, so there is a drawback in that birefringence occurs due to residual strain during molding and stress generated when fixing optical components to equipment.

[0006] For this reason, resin materials that reduce both orientation birefringence and photoelasticity in injection molded pieces and have high heat resistance have been proposed, such as a non-birefringent resin material (Patent Document 5) made of a composition containing a resin such as glutarimide acrylic resin and a graft copolymer, and a methacrylic copolymer (Patent Document 6) having a ring structure in the main chain obtained from a monomer containing a methacrylate monomer and two or more types of N-substituted maleimide monomers. However, compositions containing multiple resins that are not completely compatible as in Patent Document 5 have high haze and poor transparency as the molded body becomes thicker, so their application as optical parts is limited. In addition, although the methacrylic resin in Patent Document 6 has low orientation birefringence and photoelastic coefficient even as an injection molded body, there is room for improvement in terms of birefringence that occurs when used in molded bodies with complex shapes such as lenses and prisms whose thickness changes, or thin molded bodies such as light guide plates. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2006-308682 A [Patent Document 2] International Publication No. 2015 / 098980 [Patent Document 3] JP 2008-15199 A [Patent Document 4] JP 2006-328330 A [Patent Document 5] International Publication No. 2015 / 098775 [Patent Document 6] International Publication No. 2011 / 149088 Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention aims to provide a methacrylic resin which has high heat resistance and highly controlled birefringence and is suitable for injection molding applications, a methacrylic resin molded product containing the methacrylic resin, and an optical component or automobile component made of the methacrylic resin molded product. [Means for solving the problem]

[0009] The present inventors have conducted intensive studies to solve the problems of the conventional technology described above, and have found that the orientation birefringence of a methacrylic resin having a ring structure in the main chain does not show a linear dependence on the degree of orientation, and that even if the composition is designed so that the orientation birefringence at a certain degree of orientation is zero, it does not become zero at other degrees of orientation. The present inventors have also found that it is important to control the orientation birefringence at a higher degree of orientation than that conventionally assumed for film use as a resin material for molding an injection molded body, particularly a molded body having a complex shape such as a change in thickness or a thin-walled molded body. It has become clear that the above problem can be solved by using a resin in which the difference in the proportion of structural units having a ring structure in the main chain between the low molecular weight region and the high molecular weight region is small.

[0010] That is, the present invention is as follows. [1] An injection-molded article having a fine unevenness on its surface, the article being obtained using a composition containing a methacrylic resin including a structural unit having a ring structure in its main chain, Regarding the shape of the fine irregularities, the height or concave portion is 0.1 to 500 μm, and the pitch distance between the irregularities is 10 to 1000 μm, The methacrylic resin is The glass transition temperature is more than 120°C and not more than 160°C. the difference in abundance ratio of structural units having a ring structure in the main chain between a fraction having a peak top molecular weight of 40,000 to 50,000 and a fraction having a peak top molecular weight of 240,000 to 260,000 obtained by molecular weight fractionation is 3.0% by mass or less; Contains structural units derived from N-substituted maleimide monomers and / or glutarimide structural units, The sign of the orientation birefringence for the first orientation degree is different from the sign of the orientation birefringence for the second orientation degree having a value higher than the first orientation degree. the law of nature, The first orientation degree is 0.03, and the second orientation degree is 0.08. An injection molded article, [2 ] before The absolute value of the difference between the absolute value of the orientation birefringence when the methacrylic resin is oriented so that the orientation degree is 0.03 and the absolute value of the orientation birefringence when the methacrylic resin is oriented so that the orientation degree is 0.08 is 5.0 × 10 -5 The injection molded article according to [1], which is as follows: [ 3 ] The absolute value of the orientation birefringence when the methacrylic resin is oriented so as to have an orientation degree of 0.03 is 0.1×10 -5 Above 5.0×10 -5 is as follows: The absolute value of the orientation birefringence when oriented to a degree of orientation of 0.08 is 8.0 × 10 -5 The following is true: 2 ] An injection molded article according to the above. [ 4 ] [1] to [3], wherein a molded piece obtained by injection molding the methacrylic resin has a yellowness index (YI) of 20 or less as measured with an optical path length of 80 mm. 3 ] The injection molded article according to any one of the preceding claims. [ 5 ] The photoelastic coefficient of the methacrylic resin is -3×10 -12 ~+3×10 -12 Pa -1 [1] to [ 4 ] The injection molded article according to any one of the preceding claims. [ 6 ] [1] to [2], wherein the methacrylic resin has an average absolute value of an in-plane retardation (Re) of 3.5 nm or less in a region of 55 mm width x 40 mm length at the center of the plate when the methacrylic resin is injection molded into a plate shape of 1 mm thickness x 60 mm width x 45 mm length at a wavelength of 520 nm. 5 ] The injection molded article according to any one of the preceding claims. [ 7 ] [1]~[ 6 13. An optical component or an automobile component, comprising the injection molded article according to any one of claims 1 to 12. Effect of the Invention

[0011] According to the present invention, it is possible to provide a methacrylic resin which has high heat resistance and highly controlled birefringence and is suitable for injection molding applications, a molded article containing the methacrylic resin, and an optical part or automobile part made of the molded article. [Brief description of the drawings]

[0012] [Figure 1] 1A is a diagram showing a flat mold having a fan gate used in measuring the phase difference of an injection-molded piece in an embodiment, in which (A) shows a plan view and (B) shows a cross-sectional view taken along the line AA in (A). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Below, we will explain in detail the form for implementing the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to the following description and can be implemented in various modifications within the scope of its gist.

[0014] (Methacrylic resin) The methacrylic resin of this embodiment is a methacrylic resin containing a methacrylic acid ester monomer unit (A) and a structural unit (B) having a ring structure in the main chain. The structural unit (B) having a ring structure in the main chain is selected from a structural unit (B-1) derived from an N-substituted maleimide monomer, a glutarimide structural unit (B-2), and a lactone ring structural unit (B-3), etc. In addition, the methacrylic resin optionally contains other vinyl monomer units (C) that are copolymerizable with the methacrylic acid ester monomer.

[0015] Each monomer structural unit will be described below.

[0016] -Structural unit (A) derived from methacrylic acid ester monomer- First, the structural unit (A) derived from a methacrylic acid ester monomer will be described. The structural unit (A) derived from a methacrylic acid ester monomer is formed, for example, from a monomer selected from the methacrylic acid esters shown below. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cyclooctyl methacrylate, tricyclodecyl methacrylate, dicyclooctyl methacrylate, tricyclododecyl methacrylate, isobornyl methacrylate, phenyl methacrylate, benzyl methacrylate, 1-phenylethyl methacrylate, 2-phenoxyethyl methacrylate, 3-phenylpropyl methacrylate, and 2,4,6-tribromophenyl methacrylate. These monomers may be used alone or in combination of two or more kinds. Among the above methacrylic acid esters, methyl methacrylate and benzyl methacrylate are preferred in that the resulting methacrylic resin has excellent transparency and weather resistance. The structural unit (A) derived from a methacrylic acid ester monomer may be contained in one type or in two or more types.

[0017] The content of the structural unit (A) derived from a methacrylic acid ester monomer is preferably 50 to 97% by mass, more preferably 55 to 97% by mass, even more preferably 55 to 95% by mass, even more preferably 60 to 93% by mass, and particularly preferably 60 to 90% by mass, based on 100% by mass of the methacrylic resin, from the viewpoint of imparting sufficient heat resistance to the methacrylic resin by the structural unit (B) having a ring structure in the main chain, which will be described later. The content of the structural unit (A) derived from the methacrylic acid ester monomer is 1 H-NMR measurement and 13 It can be determined by C-NMR measurement. 1 H-NMR measurement and 13 C-NMR measurement can be carried out, for example, using CDCl3 or DMSO-d6 as a measurement solvent at a measurement temperature of 40°C.

[0018] The structural unit (B) having a ring structure in the main chain will be described below.

[0019] -Structural unit (B) having a ring structure in the main chain- --Structural unit derived from N-substituted maleimide monomer (B-1)-- Next, the structural unit (B-1) derived from an N-substituted maleimide monomer will be described. The structural unit (B-1) derived from an N-substituted maleimide monomer may be at least one selected from a monomer represented by the following formula (1) and / or a monomer represented by the following formula (2), and is preferably formed from both of the monomers represented by the following formula (1) and the following formula (2).

[0020] [ka] In formula (1), R 1 represents an arylalkyl group having 7 to 14 carbon atoms or an aryl group having 6 to 14 carbon atoms; R 2 and R 3 each independently represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms. Also, R 2 When is an aryl group, R 2 may contain a halogen as a substituent. Also, R 1 may be substituted with a substituent such as a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, or a benzyl group.

[0021] [ka] In formula (2), R 4 represents a hydrogen atom, a cycloalkyl group having 3 to 12 carbon atoms, or an alkyl group having 1 to 12 carbon atoms; R 5 and R 6 each independently represents a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0022] Specific examples are given below. Examples of the monomer represented by formula (1) include N-phenylmaleimide, N-benzylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-nitrophenyl)maleimide, and N-(2,4,6-trimethylphenyl)maleimide. Maleimide, N-(4-benzylphenyl)maleimide, N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthracenylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, 1,3,4-triphenyl-1H-pyrrole-2,5-dione, and the like. Among these monomers, N-phenylmaleimide and N-benzylmaleimide are preferred because the resulting methacrylic resin has excellent heat resistance and optical properties such as birefringence. These monomers may be used alone or in combination of two or more kinds.

[0023] Examples of the monomer represented by formula (2) include N-methylmaleimide, N-ethylmaleimide, Nn-propylmaleimide, N-isopropylmaleimide, Nn-butylmaleimide, N-isobutylmaleimide, Ns-butylmaleimide, Nt-butylmaleimide, Nn-pentylmaleimide, Nn-hexylmaleimide, Nn-heptylmaleimide, Nn-octylmaleimide, N-laurylmaleimide, and N-stearylmaleimide. Examples of maleimide include 1-cyclohexyl-3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, and 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione. Among these monomers, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-cyclohexylmaleimide are preferred because they provide excellent weather resistance to the methacrylic resin, and N-cyclohexylmaleimide is particularly preferred because it has excellent low moisture absorption, which is a requirement for optical materials in recent years. These monomers can be used alone or in combination of two or more.

[0024] In the methacrylic resin of this embodiment, it is particularly preferable to use a monomer represented by formula (1) and a monomer represented by formula (2) in combination, in order to express highly controlled birefringence characteristics. The molar ratio (B1 / B2) of the content (B1) of the structural unit derived from the monomer represented by formula (1) to the content (B2) of the structural unit derived from the monomer represented by formula (2) is preferably more than 0 and 15 or less, more preferably more than 0 and 10 or less. When the molar ratio B1 / B2 is within this range, the methacrylic resin molded article of this embodiment maintains its transparency, does not turn yellow, and does not lose its environmental resistance, and exhibits good heat resistance and good photoelastic properties.

[0025] The content of the structural unit (B-1) derived from the N-substituted maleimide monomer is not particularly limited as long as the resulting composition satisfies the glass transition temperature range of this embodiment, but is preferably in the range of 5 to 40 mass%, more preferably in the range of 5 to 35 mass%, based on 100 mass% of the methacrylic resin. Within this range, the methacrylic resin molded article can obtain a more sufficient improvement in heat resistance, and can obtain more preferable improvements in weather resistance, low water absorption, and optical properties. In addition, keeping the content of structural units derived from N-substituted maleimide monomers to 40 mass% or less is effective in preventing a decrease in the physical properties of the methacrylic resin molded article due to a decrease in the reactivity of the monomer component during the polymerization reaction and an increase in the amount of unreacted remaining monomer.

[0026] --Glutarimide structural unit (B-2)-- Methacrylic resins having glutarimide structural units in the main chain are, for example, methacrylic resins having glutarimide structural units described in JP 2006-249202 A, JP 2007-009182 A, JP 2007-009191 A, JP 2011-186482 A, Republished Patent Publication No. 2012 / 114718, and the like, and can be formed by the methods described in these publications.

[0027] The glutarimide structural unit constituting the methacrylic resin of the present embodiment may be formed after polymerization of the resin. Specifically, the glutarimide structural unit may be represented by the following general formula (3).

[0028] [ka] In the above general formula (3), preferably R 7 and R 8are each independently a hydrogen atom or a methyl group; R 9 is any one of hydrogen, methyl, butyl, and cyclohexyl groups, and more preferably, R 7 is a methyl group, and R 8 is hydrogen and R 9 is a methyl group. The glutarimide-based structural unit may include only one type, or may include a plurality of types. In the methacrylic resin having a glutarimide structural unit, the content of the glutarimide structural unit is not particularly limited as long as it satisfies the preferred glass transition temperature range for the composition of the present embodiment, but is preferably in the range of 5 to 70 mass %, more preferably in the range of 5 to 60 mass %, based on 100 mass % of the methacrylic resin. It is preferable that the content of the glutarimide structural unit is within the above range, since a resin having good moldability, heat resistance, and optical properties can be obtained. The methacrylic resin having a glutarimide structural unit may further contain an aromatic vinyl monomer unit, if necessary. The aromatic vinyl monomer is not particularly limited, but examples thereof include styrene and α-methylstyrene, with styrene being preferred. The content of aromatic vinyl units in the methacrylic resin having glutarimide structural units is not particularly limited, but is preferably 0 to 20% by mass, with the methacrylic resin having glutarimide structural units being 100% by mass. When the content of the aromatic vinyl unit is within the above range, it is possible to achieve both heat resistance and excellent photoelasticity properties, which is preferable.

[0029] --Lactone ring structural unit (B-3)-- Methacrylic resins having a lactone ring structural unit in the main chain can be formed by the methods described in, for example, JP-A Nos. 2001-151814, 2004-168882, 2005-146084, 2006-96960, 2006-171464, 2007-63541, 2007-297620, and 2010-180305. The lactone ring structural unit constituting the methacrylic resin of the present embodiment may be formed after polymerization of the resin. The lactone ring structural unit in this embodiment is preferably a six-membered ring because this provides excellent stability of the ring structure. As the 6-membered lactone ring structural unit, for example, a structure represented by the following general formula (4) is particularly preferred. [ka] In the above general formula (4), R 10 , R 11 and R 12 are each independently a hydrogen atom or an organic residue having 1 to 20 carbon atoms. Examples of the organic residue include saturated aliphatic hydrocarbon groups (alkyl groups, etc.) having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, a propyl group, etc.; unsaturated aliphatic hydrocarbon groups (alkenyl groups, etc.) having 2 to 20 carbon atoms, such as an ethenyl group, a propenyl group, etc.; aromatic hydrocarbon groups (aryl groups, etc.) having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, etc.; and groups in which one or more hydrogen atoms in these saturated aliphatic hydrocarbon groups, unsaturated aliphatic hydrocarbon groups, and aromatic hydrocarbon groups have been substituted with at least one group selected from the group consisting of a hydroxy group, a carboxyl group, an ether group, and an ester group. The lactone ring structure can be formed, for example, by copolymerizing an acrylic acid monomer having a hydroxy group with a methacrylic acid ester monomer such as methyl methacrylate to introduce a hydroxy group and an ester group or a carboxyl group into the molecular chain, and then causing dealcoholization (esterification) or dehydration condensation (hereinafter also referred to as a "cyclization condensation reaction") between the hydroxy group and the ester group or the carboxyl group. Examples of the acrylic acid monomer having a hydroxy group used in the polymerization include 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, alkyl 2-(hydroxymethyl)acrylates (e.g., methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, t-butyl 2-(hydroxymethyl)acrylate), alkyl 2-(hydroxyethyl)acrylates, etc., and preferably 2-(hydroxymethyl)acrylic acid or alkyl 2-(hydroxymethyl)acrylate, which are monomers having a hydroxyallyl moiety, and particularly preferably methyl 2-(hydroxymethyl)acrylate or ethyl 2-(hydroxymethyl)acrylate.

[0030] The content of the lactone ring structural unit in the methacrylic resin having the lactone ring structural unit in the main chain is not particularly limited as long as it satisfies the range of the glass transition temperature of the methacrylic resin of the present embodiment, but is preferably 5 to 40 mass %, and more preferably 5 to 35 mass %, relative to 100 mass % of the methacrylic resin. When the content of the lactone ring structural unit is within this range, the effects of introducing a ring structure, such as improved solvent resistance and improved surface hardness, can be achieved while maintaining moldability. The content of the lactone ring structure in the methacrylic resin can be determined by the method described in the aforementioned patent document.

[0031] From the viewpoints of heat resistance, thermal stability, strength, and fluidity of the methacrylic resin of this embodiment, the content of the structural unit (B) having a ring structure in the main chain is preferably 3 to 40 mass%, with the methacrylic resin being 100 mass%, and the lower limit is more preferably 5 mass% or more, even more preferably 7 mass% or more, and still more preferably 8 mass% or more, and the upper limit is more preferably 30 mass% or less, even more preferably 28 mass% or less, even more preferably 25 mass% or less, particularly preferably 20 mass% or less, particularly still more preferably 18 mass% or less, and most preferably less than 15 mass%.

[0032] -Other vinyl monomer units copolymerizable with methacrylic acid ester monomers (C)- Other vinyl monomer units (C) (hereinafter, sometimes referred to as (C) monomer units) copolymerizable with the methacrylic acid ester monomer that can constitute the methacrylic resin of this embodiment include aromatic vinyl monomer units (C-1), acrylic acid ester monomer units (C-2), vinyl cyanide monomer units (C-3), and monomer units other than these (C-4). The other vinyl monomer units (C) copolymerizable with the methacrylic acid ester monomer may be used alone or in combination of two or more kinds.

[0033] The monomer unit (C) can be selected appropriately depending on the properties required for the methacrylic resin. When properties such as thermal stability, fluidity, mechanical properties, and chemical resistance are particularly required, at least one selected from the group consisting of an aromatic vinyl monomer unit (C-1), an acrylic acid ester monomer unit (C-2), and a vinyl cyanide monomer unit (C-3) is suitable.

[0034] [Aromatic vinyl monomer unit (C-1)] The monomer constituting the aromatic vinyl monomer unit (C-1) constituting the methacrylic resin of this embodiment is not particularly limited, but is preferably an aromatic vinyl monomer represented by the following general formula (5).

[0035] [ka] In the general formula (4), R 13 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted, for example, with a hydroxyl group. R 14 is any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 8 carbon atoms, and an aryloxy group having 6 to 8 carbon atoms; R 2may all be the same group or different groups. 14 They may combine together to form a ring structure. n represents an integer of 0 to 5.

[0036] Specific examples of the monomer represented by the above general formula (5) include, but are not limited to, styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenylbenzene (α-methylstyrene), isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, isopropenyloctylbenzene, α-hydroxymethylstyrene, and α-hydroxyethylstyrene. Of the above, styrene and isopropenylbenzene are preferred, and styrene is more preferred from the viewpoints of imparting fluidity and reducing unreacted monomers by improving the polymerization conversion rate. These may be appropriately selected depending on the properties required for the methacrylic resin of this embodiment.

[0037] When the aromatic vinyl monomer unit (C-1) is used, its content is preferably 23% by mass or less, more preferably 20% by mass or less, even more preferably 18% by mass or less, still more preferably 15% by mass or less, and still more preferably 10% by mass or less, when the total amount of the monomer unit (A) and the structural unit (B) is taken as 100% by mass, taking into consideration the balance between heat resistance, reduction in residual monomer species, and flowability.

[0038] When the aromatic vinyl monomer unit (C-1) is used in combination with the above-mentioned maleimide structural unit (B-1), the ratio (mass ratio) of the content of the (C-1) monomer unit to the content of the (B-1) structural unit (i.e., (C-1) content / (B-1) content) is preferably 0.3 to 5 from the viewpoints of processing flowability and the effect of reducing silver streaks by reducing residual monomers. From the viewpoint of maintaining good color tone and heat resistance, the upper limit is preferably not more than 5, more preferably not more than 3, and even more preferably not more than 1. From the viewpoint of reducing residual monomers, the lower limit is preferably not less than 0.3, and more preferably not less than 0.4. The above-mentioned aromatic vinyl monomer (C-1) may be used alone or in combination of two or more kinds.

[0039] [Acrylic acid ester monomer unit (C-2)] The monomer constituting the acrylic acid ester monomer unit (C-2) constituting the methacrylic resin of this embodiment is not particularly limited, but is preferably an acrylic acid ester monomer represented by the following general formula (6).

[0040] [ka] In the general formula (6), R 15 represents a hydrogen atom or an alkoxy group having 1 to 12 carbon atoms; R 16 represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0041] As a monomer for forming the acrylic ester monomer unit (C-2), from the viewpoint of enhancing weather resistance, heat resistance, fluidity, and thermal stability in the methacrylic resin for the film of this embodiment, preferred are methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, phenyl acrylate, and the like, more preferred are methyl acrylate, ethyl acrylate, and n-butyl acrylate, and from the viewpoint of easy availability, methyl acrylate and ethyl acrylate are even more preferred. The acrylic acid ester monomer unit (C-2) may be used alone or in combination of two or more kinds.

[0042] When the acrylic acid ester monomer unit (C-2) is used, its content is preferably 5% by mass or less, and more preferably 3% by mass or less, when the total amount of the (A) monomer unit and the (B) structural unit is taken as 100% by mass, from the viewpoints of heat resistance and thermal stability.

[0043] [Cyanide vinyl monomer unit (C-3)] The monomer constituting the vinyl cyanide monomer unit (C-3) constituting the methacrylic resin of this embodiment is not particularly limited, but examples thereof include acrylonitrile, methacrylonitrile, ethacrylonitrile, vinylidene cyanide, etc., and among these, acrylonitrile is preferred from the viewpoints of ease of availability and chemical resistance. The vinyl cyanide monomer unit (C-3) may be used alone or in combination of two or more kinds.

[0044] When the vinyl cyanide monomer unit (C-3) is used, its content is preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 10% by mass or less, when the total amount of the monomer unit (A) and the structural unit (B) is taken as 100% by mass, from the viewpoint of maintaining solvent resistance and heat resistance.

[0045] [Monomer unit (C-4) other than (C-1) to (C-3)] The monomer constituting the monomer unit (C-4) other than (C-1) to (C-3) constituting the methacrylic resin of this embodiment is not particularly limited, and examples thereof include amides such as acrylamide and methacrylamide; glycidyl compounds such as glycidyl (meth)acrylate and allyl glycidyl ether; unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid, and semi-esterified products or anhydrides thereof; unsaturated alcohols such as methallyl alcohol and allyl alcohol; olefins such as ethylene, propylene, and 4-methyl-1-pentene; and vinyl compounds or vinylidene compounds other than those mentioned above, such as vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinyl pyrrolidone, and N-vinyl carbazole. Further, examples of crosslinkable compounds having a plurality of reactive double bonds include compounds in which both terminal hydroxyl groups of ethylene glycol or its oligomers are esterified with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; compounds in which hydroxyl groups of two alcohols are esterified with acrylic acid or methacrylic acid, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate; compounds in which polyhydric alcohol derivatives, such as trimethylolpropane and pentaerythritol, are esterified with acrylic acid or methacrylic acid; and polyfunctional monomers, such as divinylbenzene.

[0046] Among the monomers constituting the above-mentioned (C) monomer unit, at least one selected from the group consisting of methyl acrylate, ethyl acrylate, styrene, and acrylonitrile is preferred from the viewpoint of availability.

[0047] The content of the other vinyl monomer units (C) copolymerizable with the methacrylic acid ester monomer is 0 to 20 mass%, preferably 0 to 18 mass%, and more preferably 0 to 15 mass%, based on 100 mass% of the methacrylic resin, from the viewpoint of enhancing the effect of imparting heat resistance by the structural units (B). In particular, when a crosslinkable polyfunctional (meth)acrylate having a plurality of reactive double bonds is used as the (C) monomer unit, the content of the (C) monomer unit is preferably 0.5 mass % or less, more preferably 0.3 mass % or less, and even more preferably 0.2 mass % or less, from the viewpoint of the fluidity of the polymer.

[0048] In particular, in this embodiment, from the viewpoint of heat resistance and optical properties of the methacrylic resin molded article, when the total amount of the (B) structural unit and the (C) monomer unit is taken as 100% by mass, the content of the (B) structural unit is 45 to 100% by mass. At this time, the content of the (C) structural unit is 0 to 55% by mass. The content of the (B) structural unit is preferably 50 to 100% by mass, more preferably 50 to 90% by mass, and even more preferably 50 to 80% by mass.

[0049] The characteristics of the methacrylic resin of this embodiment will be described below.

[0050] The glass transition temperature (Tg) of the methacrylic resin in this embodiment is higher than 120° C. and 160° C. or lower. If the glass transition temperature of the methacrylic resin exceeds 120° C., it is possible to more easily obtain sufficient heat resistance required for recent optical components such as lens molded bodies, automobile components such as in-vehicle displays, and optical films for film molded bodies for liquid crystal displays. From the viewpoint of dimensional stability under the temperature of the environment in which the resin is used, the glass transition temperature (Tg) is more preferably 125° C. or higher, and even more preferably 130° C. or higher. On the other hand, when the glass transition temperature (Tg) of the methacrylic resin is 160° C. or lower, melt processing at extremely high temperatures can be avoided, thermal decomposition of the resin, etc. can be suppressed, and a good product can be obtained. For the above-mentioned reasons, the glass transition temperature (Tg) is preferably 150° C. or lower. The glass transition temperature (Tg) can be determined by measurement in accordance with JIS-K7121. Specifically, it can be measured by the method described in the examples below.

[0051] In the methacrylic resin of this embodiment containing a structural unit having a ring structure in the main chain, it is preferable that the sign of the orientation birefringence when oriented so that the orientation degree is 0.03 is different from the sign of the orientation birefringence when oriented so that the orientation degree is 0.08.

[0052] Furthermore, when the orientation degree is 0.03, the absolute value of the orientation birefringence is 0.1×10 -5 Above 5.0×10 -5 It is preferable that the value is less than 0.1×10 -5 Above 3.0×10 -5 More preferably, it is 0.3×10 or less. -5 Above 2.0×10 -5 More preferably, it is 0.5×10 or less. -5 More than 1.5 x 10 -5 It is even more preferred that: In addition, when the orientation degree is 0.08, the absolute value of the orientation birefringence is 8.0×10 -5 It is preferable that the value is less than 5.0×10 -5 More preferably, it is 0.1×10 or less. -5 Above 4.0×10 -5 More preferably, it is 0.3×10 or less. -5 Above 3.0×10 -5 It is even more preferred that: Furthermore, the absolute value of the difference between the absolute value of the orientation birefringence when the orientation degree is 0.03 and the absolute value of the orientation birefringence when the orientation degree is 0.08 is 5.0 × 10 -5 It is preferable that the value is less than 4.0×10 -5 More preferably, it is 3.0×10 or less. -5 More preferably, it is 2.0×10 or less. -5 Even more preferably, it is equal to or less than 1.0×10 -5It is even more preferred that: The orientation birefringence of the methacrylic resin can be determined specifically by the method described in the Examples below.

[0053] For example, when the orientation degree is 0.03, the orientation birefringence is 0.4×10 -5 Orientation birefringence when oriented so that the orientation degree is 0.08: -2.4×10 -5 When the resin is oriented so that the degree of orientation is 0.03, the orientation birefringence is -0.4×10 -5 Orientation birefringence when oriented to a degree of orientation of 0.08: 2.4×10 -5 The resin having the above property technically has the same meaning in that when it is molded into a body, the in-plane birefringence can be offset by the orientation distribution in the thickness direction.

[0054] The birefringence Δn is defined as follows: Δn = nx - ny (a) nx is the refractive index in the stretching direction, and ny is the refractive index in the direction perpendicular to the stretching direction. If nx is larger than ny, Δn is positive, and if it is smaller, Δn is negative. The intrinsic birefringence is Δn 0 If the degree of orientation is f, the orientation birefringence Δn or is expressed as follows: Δn or =f × Δn 0 (b)

[0055] Here, the degree of orientation f is an index that indicates the degree of orientation of the polymer main chain, and the state in which the polymer is completely oriented in one direction is represented as f=1. The orientation birefringence at this time is the intrinsic birefringence Δn 0 The degree of orientation f can be determined by infrared dichroism measurement. A methacrylic resin molded into a film is stretched, and infrared light polarized horizontally or vertically to the stretching direction is irradiated. The absorbance of the light is measured as A. ∥ , A ⊥ Then, the infrared dichroic ratio D is D=A ∥ / A ⊥(c) This is expressed as: If the angle between the direction of the vibrational transition moment related to the absorption of the functional group of interest and the orientation direction or extension direction of the main chain is α, the degree of orientation f is expressed by the following formula.

number

[0056] The present inventors have attempted to reduce birefringence in injection-molded products of methacrylic resins having a ring structure, which have a higher thickness and degree of orientation than films for conventional applications and require a higher level of birefringence reduction, by bringing both the intrinsic birefringence, which is a measure of orientation birefringence, and the photoelastic coefficient, which is a measure of photoelastic birefringence, closer to zero. In the process, we investigated resin materials that exhibit lower orientation birefringence over a higher and wider range of orientation degrees, and found that the birefringence of a methacrylic resin having a ring structure does not exhibit a linear dependence on the orientation degree. For example, even when the composition of a methacrylic resin having a ring structure is adjusted so that the orientation birefringence at a low orientation degree is zero, the orientation birefringence at a high orientation degree does not become zero. Therefore, it was found that the conventional method of selecting multiple monomers that have different signs for the intrinsic birefringence and photoelastic coefficient when made into homopolymers, combining and copolymerizing them, and adjusting the composition to reduce the orientation birefringence and photoelastic birefringence of the copolymer cannot completely eliminate the birefringence of injection-molded bodies that have a distribution of the degree of orientation inside the molded body. The reason why orientation birefringence in methacrylic resins having a ring structure shows dependence on the degree of orientation is unclear, but it is presumed that this is because the ease of movement when an external force is applied differs between methacrylic comonomer units and comonomer units having a ring structure, so that the comonomer units that are more mobile move at low orientation, and as the orientation becomes higher, the comonomer units that are less mobile also move, resulting in different ways of microscopically orienting the comonomer units at low and high degrees of orientation. Therefore, the inventors discovered that by preparing a copolymer in which the sign of the intrinsic birefringence at a degree of orientation corresponding to a region with a low orientation near the center of the thickness direction inside the injection-molded body is different from the sign of the intrinsic birefringence at a degree of orientation corresponding to a region with a high orientation slightly inside from the surface, it is possible to cancel out the orientation birefringence in the injection-molded body and reduce the birefringence of the injection-molded body.

[0057] The optimum magnitude of orientation birefringence varies depending on the shape of the injection molded product. However, when oriented so that the degree of orientation is 0.03, the absolute value of the orientation birefringence is 0.1×10 -5 Above 5.0×10 -5 When the orientation degree is 0.08, the absolute value of the orientation birefringence is 8.0×10 -5 If the thickness is less than or equal to 1.5 mm, it is particularly preferable that an injection molded article having a low birefringence can be obtained, particularly in the case of an injection molded article having a thin thickness of 1.5 mm or less, or an injection molded article having a complex shape, such as one having a variable thickness.

[0058] Photoelastic coefficient C of the methacrylic resin containing a structural unit having a ring structure in the main chain of this embodiment R The absolute value of is 3.0×10 -12 Pa -1 It is preferable that the value is less than 2.0×10 -12 Pa -1 More preferably, it is 1.0×10 -12 Pa -1 It is even more preferable that: The photoelastic coefficient is described in various publications (for example, see Chemical Review, No. 39, 1998 (published by the Academic Press Center)) and is defined by the following formulas (ia) and (ib). RIt can be seen that the closer the value of is to zero, the smaller the change in birefringence due to an external force is. C R =Δn / σ R (e) Δn = nx - ny (f) (In the formula, C R is the photoelastic coefficient, σ R is the stretching stress, Δn is the birefringence, nx is the refractive index in the stretching direction, and ny is the refractive index in the in-plane direction perpendicular to the stretching direction.) Photoelastic coefficient C of the methacrylic resin of this embodiment R The absolute value of is 3.0 × 10 -12 Pa -1 If it is equal to or less than this, birefringence caused by residual stress during injection molding, stress caused when the injection molded article is fitted into a product as a part, and the like, becomes sufficiently small. The photoelastic coefficient C of methacrylic resins is R Specifically, it can be determined by the method described in the Examples below.

[0059] In the methacrylic resin in this embodiment, the weight average molecular weight (Mw) in terms of polymethyl methacrylate measured by gel permeation chromatography (GPC) is preferably in the range of 65,000 to 220,000, more preferably in the range of 80,000 to 180,000, and even more preferably in the range of 90,000 to 150,000. When the weight average molecular weight (Mw) is within the above range, the balance between mechanical strength and flowability is excellent. Regarding the ratios among the Z-average molecular weight (Mz), weight-average molecular weight (Mw), and number-average molecular weight (Mn) as parameters representing molecular weight distribution, in the methacrylic resin of the present embodiment, taking into consideration the balance between fluidity and mechanical strength, Mw / Mn is preferably 1.5 to 3.0, more preferably 1.6 to 2.5, and even more preferably 1.6 to 2.3; Mz / Mw is preferably 1.3 to 2.0, more preferably 1.3 to 1.8, and even more preferably 1.4 to 1.7. The weight average molecular weight and number average molecular weight of the methacrylic resin can be measured by the method described in the Examples below. The sign of the orientation birefringence when oriented so that the orientation degree is 0.03 is different from the sign of the orientation birefringence when oriented so that the orientation degree is 0.08, and further, preferably, the absolute value of the orientation birefringence when oriented so that the orientation degree is 0.03 is 0.1 × 10 -5 Above 5.0×10 -5 When the orientation degree is 0.08, the absolute value of the orientation birefringence is 8.0×10 -5 A methacrylic resin containing a structural unit having a ring structure having the following characteristics tends to have a uniform composition distribution of the ring structures in the methacrylic resin. The composition distribution of the ring structure in the methacrylic resin can be determined by observing the molecular weight dependence of the composition ratio of the structural unit containing the ring structure in the methacrylic resin, specifically, by determining the abundance ratio of the structural unit having a ring structure for each component obtained by molecular weight fractionation of the methacrylic resin by preparative GPC. When the abundance ratio of the structural unit having a ring structure in the methacrylic resin component obtained by molecular weight fractionation is expressed in mass%, the difference in the abundance ratio of the structural unit having a ring structure between the fractionated component with a peak top molecular weight of 40,000 to 50,000 and the fractionated component with a peak top molecular weight of 240,000 to 260,000 is 3.0 mass% or less, preferably 2.5 mass% or less, more preferably 2.0 mass% or less, and even more preferably 1.5 mass% or less. Here, a fraction having a peak top molecular weight of 40,000 to 50,000 refers to any fraction having a peak top molecular weight in this range, and a fraction having a peak top molecular weight of 240,000 to 260,000 refers to any fraction having a peak top molecular weight in this range. The method for molecular weight fractionation of the methacrylic resin and the ratio of structural units having a ring structure in each fractionated component can be measured by the method described in the Examples below. Furthermore, the absolute value of the difference between the absolute value of the orientation birefringence when the orientation degree is 0.03 and the absolute value of the orientation birefringence when the orientation degree is 0.08 is 5.0 × 10 -5 By adjusting the composition of the structural units containing a ring structure in the methacrylic resin as described below, it is possible to obtain a methacrylic resin which can give an injection-molded article having low birefringence. By reducing the difference in the composition of the structural unit containing a ring structure between methacrylic resin components with different molecular weights and setting the composition of the structural unit containing a ring structure in the entire methacrylic resin to an appropriate value, the orientation birefringence has different signs between the low orientation degree and the high orientation degree, and the value can be suppressed. The factors that enable such control are not clear, but the following reasons are considered. That is, structural units having a ring structure that generally show a birefringence sign opposite to that of the methacrylic acid ester monomer unit have low mobility in the molecular chain. Therefore, when there is a bias in the bond composition of the structural unit containing a ring structure, the molecular chain to which a large amount of methacrylic acid ester monomer is bonded is preferentially oriented due to external stress, so that the orientation birefringence increases in one direction and it is difficult to obtain a different sign depending on the orientation degree. In addition, it is thought that there is a difference in the way that low molecular weight components and high molecular weight components are oriented due to the flow during molding, but it is also possible that the difference in orientation birefringence due to the difference in the orientation degree can be reduced by reducing the composition distribution of the ring structure.

[0060] The yellowness index (YI) at an optical path length of 80 mm of an injection-molded piece of the methacrylic resin containing a structural unit having a structural unit with a ring structure in the main chain of this embodiment is preferably 20 or less, more preferably 18 or less, even more preferably 16 or less, and even more preferably 15 or less. When the yellowness index of the methacrylic resin of the present embodiment is within the above range, a molded article having excellent color tone can be obtained. The yellowness index (YI) can be measured by the method described in the Examples below.

[0061] (Methacrylic resin manufacturing method) The method for producing the methacrylic resin of this embodiment will be described below.

[0062] In the production method of this embodiment, a batch system, a semi-batch system, or a continuous system can be used as the polymerization system. Here, the batch system is a process in which the reaction is started and proceeded after the entire amount of raw materials is charged into a reactor, and the product is recovered after the reaction is completed. The semi-batch system is a process in which either the raw materials are charged or the product is recovered simultaneously during the reaction, and the continuous system is a process in which both the raw materials are charged and the product is recovered simultaneously during the reaction. As a method for producing a methacrylic resin having a ring structure in the main chain in this embodiment, a semi-batch system in which a part of the raw materials is charged after the reaction is started is preferable from the viewpoint of precisely controlling the copolymer composition. The continuous method is not preferred as a production method in this embodiment for the following reasons. When the polymerization reaction is carried out in one complete mixing reactor, there is an advantage that the difference in monomer composition between the fractions having different molecular weights in the methacrylic resin can be reduced, but since a large amount of unreacted monomer remains after polymerization, it tends to have a negative effect on the color tone. On the other hand, when a plug flow reactor is used, the amount of unreacted monomer can be reduced, but the difference in monomer composition between the fractions having different molecular weights in the methacrylic resin tends to be large. Even when multiple complete mixing reactors or a complete mixing reactor and a plug flow reactor are combined in series, the amount of unreacted monomer can be reduced, but the difference in monomer composition between the fractions tends to be large. In the method for producing the methacrylic resin in this embodiment, polymerization of monomers by radical polymerization is used.

[0063] Hereinafter, a method for producing a methacrylic resin containing an N-substituted maleimide structural unit (B-1) as the structural unit (B) having a ring structure in the main chain will be described in detail.

[0064] Hereinafter, as an example of a method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer (hereinafter, sometimes referred to as a "maleimide copolymer"), a case where the resin is produced by radical polymerization in a semi-batch system using a solution polymerization method will be specifically described.

[0065] The polymerization solvent to be used is not particularly limited as long as it can increase the solubility of the maleimide copolymer obtained by polymerization and can appropriately maintain the viscosity of the reaction solution for the purpose of preventing gelation, etc. Specific examples of the polymerization solvent that can be used include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and isopropylbenzene; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone. Furthermore, alcohols such as methanol, ethanol, and isopropanol may be used in combination as a polymerization solvent within a range that does not inhibit dissolution of the polymerization product during polymerization.

[0066] The amount of the solvent during polymerization is not particularly limited as long as the polymerization proceeds, the precipitation of the copolymer or the monomers used does not occur during production, and the amount can be easily removed, but for example, when the total amount of the monomers to be blended is 100 parts by mass, the amount is preferably 10 to 200 parts by mass, more preferably 25 to 200 parts by mass, even more preferably 50 to 200 parts by mass, and even more preferably 50 to 150 parts by mass.

[0067] The polymerization temperature is not particularly limited as long as it is a temperature at which the polymerization proceeds, but is preferably 70 to 180° C., more preferably 80 to 160° C., even more preferably 90 to 150° C., and even more preferably 100 to 150° C. From the viewpoint of productivity, it is preferably 70° C. or higher, and is preferably 180° C. or lower in order to suppress side reactions during polymerization and to obtain a polymer with the desired molecular weight and quality.

[0068] The polymerization time is not particularly limited as long as it is a time that can obtain a required degree of polymerization at a required conversion rate, but from the viewpoint of productivity, etc., it is preferably 2 to 15 hours, more preferably 3 to 12 hours, and even more preferably 4 to 10 hours.

[0069] In the present embodiment, the polymerization conversion rate at the end of polymerization of the methacrylic resin having a structural unit derived from an N-substituted maleimide monomer in the main chain is preferably 93 to 99.9%, more preferably 95 to 99.9%, and even more preferably 97 to 99.8%. Here, the polymerization conversion rate is the ratio of the total mass of the monomers added to the polymerization system minus the total mass of the monomers remaining at the end of the polymerization to the total mass of the monomers added to the polymerization system.

[0070] Furthermore, the amount of N-substituted maleimide monomer remaining in the solution after polymerization (residual N-substituted maleimide amount) is preferably from 50 to 5000 ppm by mass, more preferably from 100 to 3000 ppm by mass, and further preferably from 200 to 1000 ppm by mass. The higher the polymerization conversion rate and the smaller the remaining amount of N-substituted maleimide, the less monomer will be circulated to the solvent recovery system, reducing the load on the purification system and increasing the unit consumption, which is economical. However, if the polymerization conversion rate is made too high or the remaining amount of N-substituted maleimide is reduced too much, the amount of colorable low-molecular-weight components will increase, which may have an adverse effect on the color tone and moldability.

[0071] During the polymerization reaction, a polymerization initiator or a chain transfer agent may be added as necessary.

[0072] As the polymerization initiator, any initiator generally used in radical polymerization can be used. Examples of the polymerization initiator include organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-t-butyl peroxide, lauroyl peroxide, benzoyl peroxide, t-butylperoxyisopropyl carbonate, t-amylperoxy-2-ethylhexanoate, t-amylperoxyisononanoate, and 1,1-di-t-butylperoxycyclohexane; azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and dimethyl-2,2'-azobisisobutyrate; and the like. These may be used alone or in combination of two or more. These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress. The amount of the polymerization initiator added may be 0.01 to 1 part by mass, and preferably 0.05 to 0.5 part by mass, relative to 100 parts by mass of the total amount of the monomers used in the polymerization.

[0073] As the chain transfer agent, any chain transfer agent used in general radical polymerization can be used, and examples thereof include mercaptan compounds such as n-butyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, etc.; halogen compounds such as carbon tetrachloride, methylene chloride, bromoform, etc.; unsaturated hydrocarbon compounds such as α-methylstyrene dimer, α-terpinene, dipentene, terpinolene, etc.; and the like. These may be used alone or in combination of two or more. These chain transfer agents may be added at any stage as long as the polymerization reaction is in progress, and there are no particular limitations on the addition stage. The amount of the chain transfer agent added may be 0.01 to 1 part by mass, and preferably 0.05 to 0.5 part by mass, based on 100 parts by mass of the total amount of monomers used in the polymerization.

[0074] In solution polymerization, it is important to reduce the dissolved oxygen concentration in the polymerization solution as much as possible. For example, the dissolved oxygen concentration is preferably 10 ppm or less. The dissolved oxygen concentration can be measured, for example, using a dissolved oxygen meter DO meter B-505 (manufactured by Iijima Electronics Co., Ltd.). The method for reducing the dissolved oxygen concentration can be appropriately selected from the following methods: bubbling an inert gas into the polymerization solution; repeatedly pressurizing a container containing the polymerization solution to about 0.2 MPa with an inert gas before polymerization and then releasing the pressure; passing an inert gas through a container containing the polymerization solution.

[0075] In the polymerization of the methacrylic resin having a ring structure unit derived from the N-substituted maleimide monomer in this embodiment, in order to obtain a desired orientation birefringence at a specific degree of orientation by controlling the distribution of ring structures in the methacrylic resin, it is preferable to narrow the copolymer composition distribution in the copolymer.

[0076] In general radical polymerization, the radical concentration and monomer concentration in the system fluctuate from the beginning to the end of the polymerization. As a result, the average molecular weight of the polymer generated at each time point differs. On the other hand, methacrylic acid ester monomers generally have a high copolymerizability ratio with respect to N-substituted maleimide, and polymerization tends to proceed first. Therefore, when the finally obtained copolymer is fractionated according to molecular weight, the ratio of monomer units in the copolymer differs between each fraction. By reducing the difference in monomer composition in copolymers with different molecular weights, the difference in orientation birefringence between low and high degrees of orientation can be suppressed. Furthermore, by controlling the overall copolymer composition, the sign of the orientation birefringence at an orientation degree of 0.03 and the sign of the orientation birefringence at an orientation degree of 0.08, which are obtained in the methacrylic resin containing a structural unit having a ring structure in the main chain of this embodiment, can be made different, and preferably, the absolute value of the orientation birefringence at an orientation degree of 0.03 is 0.1×10 -5 Above 5.0×10 -5 The absolute value of the orientation birefringence when the orientation degree is 0.08 is 8.0×10 -5 It can be as follows:

[0077] In order to reduce the difference in monomer composition in copolymers having different molecular weights, it is preferable to carry out the polymerization while additionally adding a portion of the monomer units so that the monomer composition in the polymerization system during polymerization becomes as uniform as possible.

[0078] For example, the type, amount and timing of the additionally added monomer are adjusted so that at least at one point when 60 to 70% of the total amount of the methacrylic acid ester monomer added to the polymerization system has been consumed, the difference in consumption rate with respect to each of the other monomers added to the polymerization system is preferably 10% or less, more preferably 5% or less, and even more preferably 3% or less. The consumption rate of a certain monomer at the aforementioned point in time means the proportion of that monomer consumed in the polymerization reaction to the total amount of that monomer added, and the total amount of that monomer added includes both the monomer that has already been added at the aforementioned point in time and the monomer that has not yet been added.

[0079] Furthermore, the polymerization is carried out so that the difference in final conversion rate of each monomer added to the polymerization system at the end of the polymerization is preferably 10% or less, more preferably 5% or less, and further preferably 3% or less.

[0080] The final conversion rate of the N-substituted maleimide monomer is preferably 97% or more, more preferably 98% or more, even more preferably 99% or more, and even more preferably 99.2% or more. By setting it in such a range, a methacrylic resin having excellent color tone can be obtained.

[0081] The method for recovering the polymer from the polymerization liquid obtained by solution polymerization is not particularly limited, and examples thereof include a method in which the polymerization liquid is added to an excess of a poor solvent such as a hydrocarbon solvent or an alcohol solvent in which the polymerization product obtained by polymerization is not dissolved, and then the mixture is treated with a homogenizer (emulsion dispersion), and unreacted monomers are separated from the polymerization liquid by pretreatment such as liquid-liquid extraction or solid-liquid extraction; or a method in which the polymerization solvent and unreacted monomers are separated via a process called a devolatilization process, and the polymerization product is recovered. The devolatilization step herein refers to a step of removing volatile matters such as the polymerization solvent, residual monomers, and reaction by-products under heating and reduced pressure conditions.

[0082] Examples of equipment used in the devolatilization step include a devolatilizer consisting of a tubular heat exchanger and a devolatilization tank; thin-film evaporators such as Wiblen and Exeva manufactured by Kobelco Environmental Solutions Co., Ltd., and Contra and tilted blade Contra manufactured by Hitachi, Ltd.; and a vented extruder having a residence time and surface area sufficient to exhibit devolatilization performance. A devolatilization step using a devolatilization apparatus that combines two or more of these devices can also be used.

[0083] From the viewpoint of improving the color tone, it is preferable to use a volatilization apparatus that is mainly composed of a heat exchanger and a reduced pressure vessel and does not have a rotating part in its structure. Specifically, a volatilizing apparatus can be used which is composed of a volatilizing tank having a reduced pressure vessel with a heat exchanger disposed on the upper portion thereof and a size allowing volatilization, to which a reduced pressure unit is attached, and a discharge device such as a gear pump for discharging the polymer after volatilization. In the above-mentioned volatilizing apparatus, the polymerization solution is preheated by being fed to a heated heat exchanger, such as a multi-tube heat exchanger, a plate fin heat exchanger, or a flat plate heat exchanger having a flat plate flow path and a heater, which is disposed in the upper part of the reduced pressure vessel, and then fed to a volatilizing tank which is heated and under reduced pressure, to separate and remove the polymerization solvent, the unreacted raw material mixture, the polymerization by-products, and the copolymer. The use of a volatilizing apparatus having no rotating part as described above is preferable because it allows the production of a methacrylic resin having a good color tone.

[0084] The treatment temperature in the devolatilizer is preferably 150 to 350° C., more preferably 170 to 300° C., and further preferably 200 to 280° C. By setting the temperature to be equal to or higher than the lower limit, the amount of remaining volatile matter can be suppressed, and by setting the temperature to be equal to or lower than the upper limit, coloration and decomposition of the obtained acrylic resin can be suppressed.

[0085] The degree of vacuum in the volatilizer is preferably in the range of 10 to 500 Torr, and more preferably in the range of 10 to 300 Torr. By setting the degree of vacuum to the upper limit or less, the amount of remaining volatile matter can be suppressed. Also, a degree of vacuum equal to or greater than the lower limit is practical for industrial implementation. The treatment time is appropriately selected depending on the amount of remaining volatile matter, but in order to suppress coloration and decomposition of the resulting acrylic resin, the shorter the treatment time, the better.

[0086] The polymer recovered through the devolatilization step is processed into pellets in a step called a granulation step. In the granulation process, the molten resin is extruded in the form of strands through a multi-hole die and processed into pellets by the cold cut method, the air hot cut method, or the underwater cut method.

[0087] When a vented extruder is used as the volatilizing device, the volatilizing step may be combined with the granulation step. In other volatilizing devices, the molten resin may be pressurized by a gear pump or the like, discharged, and simultaneously passed through a multi-hole die to form strands, thereby granulating the resin.

[0088] Next, an example of a method for producing a methacrylic resin having a glutarimide structural unit will be described.

[0089] Methacrylic resins having glutarimide structural units in the main chain are, for example, methacrylic resins having glutarimide structural units described in JP 2006-249202 A, JP 2007-009182 A, JP 2007-009191 A, JP 2011-186482 A, WO 2012 / 114718 A, and the like, and can be formed by the methods described in these publications. Hereinafter, as an example of a method for producing a methacrylic resin having a glutarimide structural unit, a method for producing the resin by radical polymerization using a solution polymerization method will be specifically described.

[0090] First, a (meth)acrylic acid ester such as methyl methacrylate is polymerized to produce a (meth)acrylic acid ester polymer. When an aromatic vinyl unit is to be contained in a methacrylic resin having a glutarimide structural unit, a (meth)acrylic acid ester and an aromatic vinyl (e.g., styrene) are copolymerized to produce a (meth)acrylic acid ester-aromatic vinyl copolymer.

[0091] Next, the (meth)acrylic acid ester polymer or the methacrylic acid ester-aromatic vinyl copolymer is reacted with an imidizing agent to carry out an imidization reaction (imidization step), thereby producing a methacrylic resin having a glutarimide structural unit.

[0092] The imidizing agent is not particularly limited as long as it can generate the glutarimide structural unit represented by the general formula (3) above. Specifically, the imidizing agent may be ammonia or a primary amine. Examples of the primary amine include aliphatic hydrocarbon group-containing primary amines such as methylamine, ethylamine, n-propylamine, i-propylamine, n-butylamine, i-butylamine, tert-butylamine, and n-hexylamine; alicyclic hydrocarbon group-containing primary amines such as cyclohexylamine; and the like. Of the above imidizing agents, ammonia, methylamine and cyclohexylamine are preferred from the standpoint of cost and physical properties, with methylamine being particularly preferred.

[0093] In this imidization step, the content of glutarimide structural units in the resulting methacrylic resin having glutarimide structural units can be adjusted by adjusting the ratio of the imidization agent added.

[0094] The method for carrying out the imidization reaction is not particularly limited, and a conventionally known method can be used. For example, the imidization reaction can be carried out using an extruder or a batch-type reaction tank. The extruder is not particularly limited, but for example, a single screw extruder, a twin screw extruder, a multi-screw extruder, etc. can be used.

[0095] Among these, it is preferable to use a twin-screw extruder, which can promote mixing of the raw material polymer and the imidizing agent. Examples of twin-screw extruders include non-intermeshing co-rotating, intermeshing co-rotating, non-intermeshing counter-rotating, and intermeshing counter-rotating.

[0096] The above-mentioned extruders may be used alone or in combination of a plurality of extruders connected in series. It is particularly preferable to equip the extruder to be used with a vent port capable of reducing the pressure to below atmospheric pressure, since this makes it possible to remove by-products of the reaction such as the imidizing agent, methanol, and the like, or monomers.

[0097] In producing a methacrylic resin having a glutarimide structural unit, in addition to the above-mentioned imidization step, an esterification step of treating the carboxyl group of the resin with an esterification agent such as dimethyl carbonate can be included. In this case, a catalyst such as trimethylamine, triethylamine, or tributylamine can also be used in combination for the treatment. The esterification step can be carried out, for example, by using an extruder or a batch-type reaction tank, in the same manner as in the imidization step. In order to remove excess esterification agent, by-products such as methanol, or monomers, the apparatus used is preferably equipped with a vent port capable of reducing the pressure to atmospheric pressure or lower.

[0098] The methacrylic resin that has been subjected to the imidization step and, if necessary, the esterification step is melted and extruded in the form of strands from an extruder equipped with a multi-hole die, and processed into pellets by a cold cut method, an in-air hot cut method, an underwater cut method, or the like. In order to reduce the number of foreign matters in the resin, it is also preferable to use a method in which the methacrylic resin is dissolved in an organic solvent such as toluene, methyl ethyl ketone, or methylene chloride, the obtained methacrylic resin solution is filtered, and then the organic solvent is removed.

[0099] From the viewpoint of reducing the difference in the composition of glutarimide ring structural units between methacrylic resin components having glutarimide structural units with different molecular weights, and having different signs of orientation birefringence between low and high degrees of orientation, and suppressing the value, it is preferable to imidize a solution of a (meth)acrylic acid ester polymer or the above-mentioned methacrylic acid ester-aromatic vinyl copolymer in a batch reaction tank. The reason why a uniform ring structure composition can be obtained by imidizing in a solution state is not clear, but it is thought that this is because the mixability of the imidizing agent and the polymer is improved compared to when the imidization reaction is performed in an extruder, and the contact frequency between the imidizing agent and the polymer is improved regardless of the molecular weight of the polymer. On the other hand, when the cyclization reaction is performed in an extruder, the contact frequency with the polymer terminal with high mobility is high, so that the polymer component with a low molecular weight and a high terminal ratio is more likely to be cyclized.

[0100] The imidization reaction is preferably carried out at 130 to 250° C., more preferably 150 to 230° C. The reaction time is preferably 10 minutes to 5 hours, more preferably 30 minutes to 2 hours. After the imidization step, an esterification step is carried out as necessary, followed by a devolatilization and granulation step.

[0101] From the viewpoint of improving the color tone, it is preferable to use a volatilization apparatus that is mainly composed of a heat exchanger and a reduced pressure vessel and does not have a rotating part in its structure. Specifically, a volatilizing apparatus can be used which is composed of a volatilizing tank having a reduced pressure vessel with a heat exchanger disposed on the upper portion thereof and a size allowing volatilization, to which a reduced pressure unit is attached, and a discharge device such as a gear pump for discharging the polymer after volatilization. In the above-mentioned volatilizing apparatus, the polymerization solution is preheated by being fed to a heated heat exchanger, such as a multi-tube heat exchanger, a plate fin heat exchanger, or a flat plate heat exchanger having a flat plate flow path and a heater, which is disposed in the upper part of the reduced pressure vessel, and then fed to a volatilizing tank which is heated and under reduced pressure, to separate and remove the polymerization solvent, the unreacted raw material mixture, the polymerization by-products, and the copolymer. The use of a volatilizing apparatus having no rotating part as described above is preferable because it allows the production of a methacrylic resin having a good color tone.

[0102] Hereinafter, a method for producing a methacrylic resin containing a lactone ring structural unit (B-2) as the structural unit (B) having a ring structure in the main chain will be described in detail.

[0103] Methacrylic resins having a lactone ring structural unit in the main chain can be formed by the methods described in, for example, JP-A Nos. 2001-151814, 2004-168882, 2005-146084, 2006-96960, 2006-171464, 2007-63541, 2007-297620, and 2010-180305.

[0104] As an example of a method for producing a methacrylic resin having a lactone ring structural unit, a method for producing the resin by radical polymerization using a solution polymerization method will be specifically described below.

[0105] In the present embodiment, the method for producing the methacrylic resin having the lactone ring structural unit (B-2) in the main chain is preferably solution polymerization using a solvent in order to promote the cyclization reaction. Here, the lactone ring structure may be formed by a cyclization reaction after polymerization.

[0106] The methacrylic resin having a lactone ring structural unit in this embodiment can be obtained by carrying out a cyclization reaction after the completion of the polymerization reaction. Therefore, it is preferable to subject the polymerization reaction liquid to the lactone cyclization reaction while still containing the solvent, without removing the polymerization solvent from the polymerization reaction liquid. When the copolymer obtained by polymerization is heat-treated, a cyclization condensation reaction occurs between the hydroxyl groups (hydroxyl groups) and ester groups present in the molecular chain of the copolymer, forming a lactone ring structure. In the heat treatment for forming the lactone ring structure, a reaction apparatus equipped with a vacuum device or a volatilizing device, an extruder equipped with a volatilizing device, or the like can be used to remove alcohol that may be by-produced by the cyclocondensation.

[0107] When forming the lactone ring structure, a heat treatment may be carried out using a cyclization condensation catalyst, if necessary, in order to promote the cyclization condensation reaction. Specific examples of the cyclization condensation catalyst include monoalkyl phosphite, dialkyl ester, or triester phosphites such as methyl phosphite, ethyl phosphite, phenyl phosphite, dimethyl phosphite, diethyl phosphite, diphenyl phosphite, trimethyl phosphite, and triethyl phosphite; monoalkyl phosphates, dialkyl esters, or trialkyl esters such as methyl phosphate, ethyl phosphate, 2-ethylhexyl phosphate, octyl phosphate, isodecyl phosphate, lauryl phosphate, stearyl phosphate, isostearyl phosphate, dimethyl phosphate, diethyl phosphate, di-2-ethylhexyl phosphate, diisodecyl phosphate, dilauryl phosphate, distearyl phosphate, diisostearyl phosphate, trimethyl phosphate, triethyl phosphate, triisodecyl phosphate, trilauryl phosphate, tristearyl phosphate, and triisostearyl phosphate; and the like. These may be used alone or in combination of two or more.

[0108] The amount of the cyclization condensation catalyst used is not particularly limited, but is, for example, preferably 0.01 to 3 parts by mass, and more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the methacrylic resin. If the amount of the catalyst used is less than 0.01 parts by mass, the reaction rate of the cyclization condensation reaction may not be sufficiently improved, whereas if the amount of the catalyst used is more than 3 parts by mass, the resulting polymer may be colored or crosslinked, making melt molding difficult.

[0109] The timing of adding the cyclization condensation catalyst is not particularly limited, and for example, it may be added at the beginning of the cyclization condensation reaction, or during the reaction, or it may be added at both times. When the cyclization condensation reaction is carried out in the presence of a solvent, it is also preferable to simultaneously carry out devolatilization. The apparatus used when the cyclocondensation reaction and the devolatilization step are carried out simultaneously is not particularly limited, but a devolatilization apparatus consisting of a heat exchanger and a devolatilization tank, an extruder equipped with a vent, or an apparatus in which a devolatilization apparatus and an extruder are arranged in series is preferable, and a twin-screw extruder equipped with a vent is more preferable. The vented twin-screw extruder used is preferably one having a plurality of vent ports.

[0110] When a vented extruder is used, the reaction temperature is preferably 150 to 350° C., more preferably 200 to 300° C. If the reaction temperature is less than 150° C., the cyclization condensation reaction may be insufficient, resulting in a large amount of residual volatile matter. Conversely, if the reaction temperature exceeds 350° C., the resulting polymer may become discolored or decomposed. When using a vented extruder, the degree of vacuum is preferably 10 to 500 Torr, more preferably 10 to 300 Torr. If the degree of vacuum exceeds 500 Torr, volatile matter may easily remain. Conversely, if the degree of vacuum is less than 10 Torr, industrial implementation may be difficult.

[0111] When the above cyclization condensation reaction is carried out, it is also preferred to add an alkaline earth metal and / or amphoteric metal salt of an organic acid during granulation for the purpose of deactivating the remaining cyclization condensation catalyst. Examples of the alkaline earth metal and / or amphoteric metal salt of an organic acid that can be used include calcium acetylacetate, calcium stearate, zinc acetate, zinc octoate, and zinc 2-ethylhexylate.

[0112] After the cyclocondensation reaction step, the methacrylic resin is molten and extruded in the form of strands from an extruder equipped with a multi-hole die, and processed into pellets by a cold cut method, an in-air hot cut method, or an underwater cut method. The lactonization for forming the lactone ring structural unit may be carried out after the production of the resin and before the production of the resin composition (described later), or may be carried out during the production of the resin composition, together with melt-kneading of the resin and components other than the resin.

[0113] The methacrylic resin in the present embodiment preferably has at least one ring structural unit selected from the group consisting of a structural unit derived from an N-substituted maleimide monomer, a glutarimide structural unit, and a lactone ring structural unit. Among these, it is particularly preferable that the methacrylic resin has a structural unit derived from an N-substituted maleimide monomer, since optical properties such as the photoelastic coefficient can be highly controlled without blending with other thermoplastic resins.

[0114] (Methacrylic resin composition) The methacrylic resin composition of the present embodiment may include a methacrylic resin composition containing the methacrylic resin of the present embodiment described above. The methacrylic resin composition may optionally contain additives in addition to the methacrylic resin of the present embodiment described above, and may also contain thermoplastic resins, rubber polymers, etc. other than the methacrylic resin.

[0115] -Additives- The methacrylic resin composition according to the present embodiment may contain various additives within the range that does not significantly impair the effects of the present invention. The additives are not particularly limited, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, release agents, other thermoplastic resins, softeners / plasticizers such as paraffinic process oil, naphthenic process oil, aromatic process oil, paraffin, organic polysiloxane, and mineral oil, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, reinforcing agents such as glass fibers, carbon fibers, and metal whiskers, colorants, organic phosphorus compounds such as phosphites, phosphonites, and phosphate esters, other additives, and mixtures thereof.

[0116] --Antioxidants-- The methacrylic resin composition according to the present embodiment preferably contains an antioxidant that suppresses deterioration and coloration during molding or use. The antioxidant is not limited to the following, but examples thereof include hindered phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. The methacrylic resin of the present embodiment is suitably used in various applications such as melt extrusion, injection molding, and film molding. The heat history during processing varies depending on the processing method, ranging from about several tens of seconds in an extruder to several tens of minutes to several hours in the molding processing of thick-walled products and sheet molding. When subjected to a long-term heat history, it is necessary to increase the amount of heat stabilizer added in order to obtain the desired heat stability. From the viewpoint of suppressing bleed-out of the heat stabilizer and preventing the film from sticking to the roll during film formation, it is preferable to use multiple types of heat stabilizers in combination, for example, it is preferable to use at least one selected from a phosphorus-based antioxidant and a sulfur-based antioxidant in combination with a hindered phenol-based antioxidant. These antioxidants may be used alone or in combination of two or more.

[0117] Examples of the hindered phenol-based antioxidant include, but are not limited to, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[ 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylin)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2 ,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamine)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, and the like. In particular, pentaerythritol terakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate are preferred.

[0118] In addition, as the hindered phenol-based antioxidant as the antioxidant, a commercially available phenol-based antioxidant may be used. Examples of such commercially available phenol-based antioxidants include, but are not limited to, Irganox 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by BASF), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), Irganox 1330 (Irganox 1330: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), and the like. 1330: 3,3',3'',5,5',5''-hexa-t-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF), Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF), Irganox 3125 (Irganox 3125, manufactured by BASF), Adeka STAB AO-60 (pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by ADEKA), Adeka STAB AO-80 (3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, manufactured by ADEKA), Sumilizer BHT (Sumilizer BHT, manufactured by Sumitomo Chemical), Cyanox 1790 (Cyanox 1790, manufactured by Cytec), Sumilizer GA-80 (Sumilizer GA-80, manufactured by Sumitomo Chemical), Sumilizer GS (Sumilizer Examples of such compounds include GS (2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical), Sumilizer GM (2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, manufactured by Sumitomo Chemical), and Vitamin E (manufactured by Eisai). Among these commercially available phenolic antioxidants, Irganox 1010, Adeka STAB AO-60, Adeka STAB AO-80, Irganox 1076, Sumilizer GS, and the like are preferred from the viewpoint of the effect of imparting thermal stability to the resin. These may be used alone or in combination of two or more.

[0119] In addition, examples of the phosphorus-based antioxidant as the antioxidant include, but are not limited to, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, tetrakis(2,4-di-t-butylphenyl)(1,1-biphenyl)-4,4'-diyl bisphosphonite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methyl phenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetrakis(2,4-t-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphonite, di-t-butyl-m-cresyl-phosphonite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, and the like. Furthermore, commercially available phosphorus-based antioxidants may be used as the phosphorus-based antioxidant. Examples of commercially available phosphorus-based antioxidants include, but are not limited to, Irgafos 168 (Irgafos 168: tris(2,4-di-t-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, manufactured by BASF), ADK STAB 329K (ADK STAB-229K, manufactured by ADEKA), ADK STAB PEP-36 (ADK STAB PEP-36, manufactured by ADEKA), ADK STAB PEP-36A, ADK STAB PEP-8, ADK STAB HP-10, ADK STAB HP-10, ADK STAB 2112, manufactured by ADEKA, ADK STAB 1178, manufactured by ADEKA, ADK STAB 1500, manufactured by ADEKA, Sandstab P-EPQ, manufactured by Clariant, Weston 618, manufactured by GE, Weston 619G, manufactured by GE, Ultranox 626, manufactured by GE, Sumilizer GP GP: 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical Co., Ltd.), HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, manufactured by Sanko Co., Ltd.), and the like. Among these commercially available phosphorus-based antioxidants, from the viewpoint of the effect of imparting thermal stability to the resin and the effect of using them in combination with various other antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB 1178 are preferred, with ADK STAB PEP-36A and ADK STAB PEP-36 being particularly preferred. These phosphorus-based antioxidants may be used alone or in combination of two or more kinds.

[0120] In addition, examples of the sulfur-based antioxidant as the antioxidant include, but are not limited to, 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), 2,4-bis(octylthiomethyl)-6-methylphenol (Irganox 1520L, manufactured by BASF), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1 ,3-diylbis[3-dodecylthio]propionate] (ADEKA STAB AO-412S, manufactured by ADEKA Corporation), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (ChemiNox PLS, manufactured by Chemipro Chemical Co., Ltd.), and di(tridecyl) 3,3'-thiodipropionate (AO-503, manufactured by ADEKA Corporation). Among these commercially available sulfur antioxidants, ADK STAB AO-412S and Cheminox PLS are preferred from the viewpoints of the effect of imparting thermal stability to the resin, the effect of using them in combination with various antioxidants, and ease of handling. These sulfur-based antioxidants may be used alone or in combination of two or more kinds.

[0121] The content of the antioxidant may be any amount that provides the effect of improving thermal stability. If the content is excessive, problems such as bleeding out during processing may occur. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, still more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin.

[0122] The timing of adding the antioxidant is not particularly limited, and examples thereof include a method of adding the antioxidant to a monomer solution before polymerization and then initiating polymerization, a method of adding the antioxidant to a polymer solution after polymerization and mixing it and then subjecting it to a devolatilization step, a method of adding the antioxidant to a molten polymer after devolatilization and then mixing it and then pelletizing it, a method of adding the antioxidant when the pellets after devolatilization and pelletization are melt-extruded again, etc. Among these, from the viewpoint of preventing thermal deterioration and coloration in the devolatilization step, it is preferable to add the antioxidant to a polymer solution after polymerization and mix it, add it before the devolatilization step, and then subject it to the devolatilization step.

[0123] --Hindered amine light stabilizer-- The methacrylic resin composition of the present embodiment may contain a hindered amine light stabilizer. The hindered amine light stabilizer is not particularly limited, but is preferably a compound containing three or more ring structures. Here, the ring structure is preferably at least one selected from the group consisting of an aromatic ring, an aliphatic ring, an aromatic heterocycle, and a non-aromatic heterocycle, and when one compound has two or more ring structures, they may be the same or different from each other.

[0124] Examples of the hindered amine light stabilizer include, but are not limited to, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, N ,N'-Bis(2,2,6,6-tetramethyl-4-piperidyl)-N,N'-diformylhexamethylenediamine, polycondensation product of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{2,2,6,6-tetramethyl- 4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, 1,2,2,6,6-pentamethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5. reaction products of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, reaction products of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, bis(1-undecaneoxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, and 2,2,6,6-tetramethyl-4-piperidyl methacrylate. Among these, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, a polycondensate of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl} Preferred are {2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], a reaction product of 1,2,2,6,6-pentamethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, and a reaction product of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol.

[0125] The content of the hindered amine light stabilizer may be any amount that provides the effect of improving light stability. If the content is excessive, problems such as bleeding out during processing may occur. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, still more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin.

[0126] --Ultraviolet absorber-- The methacrylic resin composition of the present embodiment may contain an ultraviolet absorber. The ultraviolet absorbent is not particularly limited, but is preferably an ultraviolet absorbent having a maximum absorption wavelength of 280 to 380 nm, and examples thereof include benzotriazole-based compounds, benzotriazine-based compounds, benzophenone-based compounds, oxybenzophenone-based compounds, benzoate-based compounds, phenol-based compounds, oxazole-based compounds, cyanoacrylate-based compounds, and benzoxazinone-based compounds.

[0127] Benzotriazole compounds include 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4,6-di-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1 ,3,3-tetramethylbutyl)phenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidylmethyl)phenol, methyl 3-(3-(2H-benzotriazol-2-yl)-5-t-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 reaction product, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-C7-9 side chain and linear alkyl esters. Among these, benzotriazole-based compounds having a molecular weight of 400 or more are preferred, and examples of commercially available products include Kemisorb (registered trademark) 2792 (manufactured by Chemipro Chemicals), Adeka STAB (registered trademark) LA31 (manufactured by ADEKA Corporation), and Tinuvin (registered trademark) 234 (manufactured by BASF).

[0128] Benzotriazine compounds include 2-mono(hydroxyphenyl)-1,3,5-triazine compounds, 2,4-bis(hydroxyphenyl)-1,3,5-triazine compounds, and 2,4,6-tris(hydroxyphenyl)-1,3,5-triazine compounds. Specific examples of the benzotriazine compounds include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl). )-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4 -diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxy)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3-5-triazine, 2,4,6-tris(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy -4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4- propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,Examples of the tris(2-hydroxy-3-methyl-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine include 6-tris(2-hydroxy-3-methyl-4-methoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, and 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine. As the benzotriazine compound, commercially available products may be used, such as Kemisorb 102 (manufactured by Chemipro Chemicals), LA-F70 (manufactured by ADEKA Corporation), LA-46 (manufactured by ADEKA Corporation), TINUVIN 405 (manufactured by BASF), TINUVIN 460 (manufactured by BASF), TINUVIN 479 (manufactured by BASF), and TINUVIN 1577FF (manufactured by BASF). Among these, ultraviolet absorbers having a 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-alkyloxy-2-hydroxypropyloxy)-5-α-cumylphenyl]-s-triazine skeleton (where "alkyloxy" refers to a long-chain alkyloxy group such as octyloxy, nonyloxy, decyloxy, etc.) are more preferably used because of their high compatibility with acrylic resins and excellent ultraviolet absorption properties.

[0129] As the ultraviolet absorber, from the viewpoints of compatibility with the resin and volatility upon heating, in particular, benzotriazole-based compounds and benzotriazine-based compounds having a molecular weight of 400 or more are preferred, and from the viewpoint of suppressing decomposition of the ultraviolet absorber itself due to heating during extrusion processing, benzotriazine-based compounds are particularly preferred.

[0130] The melting point (Tm) of the ultraviolet absorber is preferably 80° C. or higher, more preferably 100° C. or higher, even more preferably 130° C. or higher, and even more preferably 160° C. or higher. The ultraviolet absorber preferably has a weight loss rate of 50% or less, more preferably 30% or less, even more preferably 15% or less, even more preferably 10% or less, and even more preferably 5% or less, when heated from 23°C to 260°C at a rate of 20°C / min.

[0131] These ultraviolet absorbents may be used alone or in combination of two or more. By using two types of ultraviolet absorbents with different structures in combination, it is possible to absorb ultraviolet rays over a wide wavelength range.

[0132] The content of the ultraviolet absorbing agent is not particularly limited as long as it does not impair heat resistance, moist heat resistance, thermal stability, and moldability and exerts the effects of the present invention, but is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass or less, more preferably 0.25 to 3 parts by mass, and even more preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of the methacrylic resin. When it is within this range, the balance between ultraviolet absorbing performance, moldability, etc. is excellent.

[0133] --Release agent-- The methacrylic resin composition of the present embodiment may contain a release agent. Examples of the release agent include, but are not limited to, fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon-based lubricants, alcohol-based lubricants, polyalkylene glycols, carboxylates, and hydrocarbon paraffin-based mineral oils.

[0134] The fatty acid ester that can be used as the release agent is not particularly limited, and any of the conventionally known fatty acid esters can be used. Examples of fatty acid esters that can be used include ester compounds of fatty acids having 12 to 32 carbon atoms, such as lauric acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, arachic acid, and behenic acid, with monohydric aliphatic alcohols, such as palmityl alcohol, stearyl alcohol, and behenyl alcohol, and polyhydric aliphatic alcohols, such as glycerin, pentaerythritol, dipentaerythritol, and sorbitan; and complex ester compounds of fatty acids, polybasic organic acids, and monohydric aliphatic alcohols or polyhydric aliphatic alcohols. Examples of such fatty acid ester lubricants include cetyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glycerin monocaprylate, glycerin monocaprate, glycerin monolaurate, glycerin monopalmitate, glycerin dipalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, glycerin monooleate, glycerin dioleate, glycerin trioleate, glycerin monolinoleate, and the like. glycerin monobehenate, glycerin mono 12-hydroxystearate, glycerin di 12-hydroxystearate, glycerin tri 12-hydroxystearate, glycerin diacetomonostearate, glycerin citrate fatty acid ester, pentaerythritol adipic acid stearate, partially saponified montanic acid ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, and sorbitan tristearate. These fatty acid ester-based lubricants can be used alone or in combination of two or more. Examples of commercially available products include the Rikemal series, Poem series, Rikestar series, and Rikemaster series manufactured by Riken Vitamin Co., Ltd., and the Excel series, Leodor series, Exepar series, and Coconard series manufactured by Kao Corporation, and more specific examples include Rikemal S-100, Rikemal H-100, Poem V-100, Rikemal B-100, Rikemal HC-100, Rikemal S-200, Poem B-200, Rikestar EW-200, Rikestar EW-400, Excel S-95, and Leodor MS-50.

[0135] There are also no particular limitations on the fatty acid amide-based lubricant, and any of the conventionally known lubricants can be used. Examples of fatty acid amide lubricants include saturated fatty acid amides such as lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, and hydroxystearic acid amide; unsaturated fatty acid amides such as oleic acid amide, erucic acid amide, and ricinoleic acid amide; substituted amides such as N-stearyl stearic acid amide, N-oleyl oleic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, and N-oleyl palmitic acid amide; methylol amides such as methylol stearic acid amide and methylol behenic acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, and ethylene bisstearic acid amide (ethylene saturated fatty acid bisamides such as ethylene bisstearylamide, ethylene bisisostearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bishydroxystearic acid amide, N,N'-distearyl adipamide, and N,N'-distearyl sebacic acid amide; unsaturated fatty acid bisamides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipamide, and N,N'-dioleyl sebacic acid amide; and aromatic bisamides such as m-xylylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide. These fatty acid amide-based release agents can be used alone or in combination of two or more. Examples of commercially available products include the Diamid series (manufactured by Nippon Kasei Co., Ltd.), the Amide series (manufactured by Nippon Kasei Co., Ltd.), the Nikka Amide series (manufactured by Nippon Kasei Co., Ltd.), the Methylol Amide series, the Bis Amide series, the Slipax series (manufactured by Nippon Kasei Co., Ltd.), the Kaowax series (manufactured by Kao Corporation), the Fatty Acid Amide series (manufactured by Kao Corporation), and ethylene bis stearic acid amides (manufactured by Dainichi Chemical Industry Co., Ltd.).

[0136] The fatty acid metal salt refers to a metal salt of a higher fatty acid, and examples thereof include lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexoate, lead stearate, dibasic lead stearate, lead naphthenate, calcium 12-hydroxystearate, and lithium 12-hydroxystearate. Of these, calcium stearate, magnesium stearate, and zinc stearate are particularly preferred because the resulting transparent resin composition has excellent processability and extremely excellent transparency. Examples of commercially available products include the SZ series, SC series, SM series, and SA series manufactured by Sakai Chemical Industry Co., Ltd. When the fatty acid metal salt is used, its content is preferably 0.2% by mass or less relative to 100% by mass of the methacrylic resin composition, from the viewpoint of maintaining transparency.

[0137] The above-mentioned release agents may be used alone or in combination of two or more kinds.

[0138] The release agent to be used is preferably one having a decomposition onset temperature of 200° C. or higher. Here, the decomposition onset temperature can be measured based on the 1% mass loss temperature by TGA. The content of the release agent may be an amount that can obtain the effect as a release agent, and if the content is excessive, problems such as bleed-out during processing and extrusion failure due to screw slippage may occur, so the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, even more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin. When the release agent is added in the amount within the above range, the decrease in transparency due to the addition of the release agent is suppressed, and there is a tendency that release failure during injection molding and sticking to a metal roll during sheet molding are suppressed, so this is preferable.

[0139] -Other thermoplastic resins- The methacrylic resin composition of the present embodiment may contain a thermoplastic resin other than the methacrylic resin for the purpose of adjusting the birefringence or improving flexibility without impairing the object of the present invention. Other thermoplastic resins include, for example, polyacrylates such as polybutyl acrylate; styrene-based polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, and acrylonitrile-butadiene-styrene block copolymer; and further, for example, acrylic rubber particles having a 3-4 layer structure described in JP-A-59-202213, JP-A-63-27516, JP-A-51-129449, JP-A-52-56150, etc.; rubbery polymers disclosed in JP-B-60-17406 and JP-A-8-245854; methacrylic rubber-containing graft copolymer particles obtained by multistage polymerization described in WO 2014-002491; and the like. Among these, from the viewpoint of obtaining good optical properties and mechanical properties, rubber-containing graft copolymer particles having a graft portion on their surface layer made of a composition compatible with styrene-acrylonitrile copolymers and methacrylic resins containing a structural unit (X) having a ring structure in the main chain are preferred. The average particle size of the above-mentioned acrylic rubber particles, methacrylic rubber-containing graft copolymer particles, and rubber polymer is preferably 0.03 to 1 μm, and more preferably 0.05 to 0.5 μm, from the viewpoint of improving the impact strength and optical properties of the molded article obtained from the composition of this embodiment.

[0140] The content of the other thermoplastic resin is preferably 0 to 50 parts by mass, and more preferably 0 to 25 parts by mass, based on 100 parts by mass of the methacrylic resin.

[0141] (Methacrylic resin composition manufacturing method) Examples of methods for producing a methacrylic resin composition include a method of kneading using a kneader such as an extruder, a heating roll, a kneader, a roller mixer, or a Banbury mixer. Among these, kneading using an extruder is preferred in terms of productivity. The kneading temperature may be in accordance with the preferred processing temperature of the polymer constituting the methacrylic resin or the other resin to be mixed, and is generally in the range of 140 to 300°C, preferably 180 to 280°C. In addition, it is preferable to provide a vent port in the extruder in order to reduce volatile content. Glass transition temperature (Tg), weight average molecular weight (Mw), number average molecular weight (Mn), orientation birefringence, and photoelastic coefficient C for methacrylic resin compositions R may be the same as described above for the methacrylic resin.

[0142] (Molded body) The molded article of the present embodiment may contain the methacrylic resin of the present embodiment, or may contain the methacrylic resin composition of the present embodiment.

[0143] (Method of Manufacturing Molded Product) As a method for producing the molded article of the present embodiment, various molding methods such as extrusion molding, injection molding, compression molding, calendar molding, inflation molding, blow molding, etc. Among these, it is preferable to apply injection molding and injection compression molding from the viewpoint of productivity. Typically, injection molding consists of (1) an injection process in which resin is melted and the molten resin is filled into the cavity of a temperature-controlled mold; (2) a pressure holding process in which pressure is applied inside the cavity until the gate is sealed, and an amount of resin is injected equivalent to the amount of molten resin filled in the injection process that comes into contact with the mold and cools and shrinks; (3) a cooling process in which the molded product is held until the resin has cooled after the pressure holding process is released; and (4) the mold is opened and the cooled molded product is removed.

[0144] In this case, the molding temperature is preferably in the range of Tg+100° C. to Tg+160° C., and more preferably in the range of Tg+110° C. to Tg+150° C., based on the glass transition temperature of the methacrylic resin composition. Here, the molding temperature refers to the controlled temperature of a band heater wrapped around the injection nozzle. The mold temperature is preferably in the range of Tg-70°C to Tg, and more preferably in the range of Tg-50°C to Tg-20°C, based on the glass transition temperature (Tg) of the methacrylic resin composition.

[0145] The injection speed can be appropriately selected depending on the thickness and dimensions of the injection molded article to be obtained, and can be appropriately selected, for example, from the range of 200 to 1000 mm / sec. The pressure for holding can be appropriately selected depending on the shape of the injection molded article to be obtained, and can be appropriately selected, for example, within the range of 30 to 120 MPa. In the case of a thin-walled molded article with a fast solidification speed, holding pressure may not be applied. The pressure for holding the pressure referred to here is the pressure maintained by a screw for further feeding the molten resin from the gate after the molten resin has been filled.

[0146] Injection compression molding is an injection molding method in which the mold is opened slightly before the start of injection molding, and molten resin is filled into the mold at high speed and low pressure. After that, the mold clamping pressure is increased at high speed and a compression and holding pressure process is added to uniformly hold the pressure over the entire surface of the resin. This makes it possible to mold molded articles with excellent surface and optical properties. When attempting to obtain a thinner injection molded article, for example one having a thickness of less than 1 mm and a diagonal dimension of more than 100 mm, it is particularly preferable to employ injection compression molding, since this method produces a molded article with excellent optical properties and color tone.

[0147] In addition, when the injection molded article obtained by using the methacrylic resin composition of the present embodiment is used as a light guide plate, the surface of the molded article may be provided with fine irregularities. By providing such fine irregularities, it is preferable that a reflective layer is not required to be provided by printing or the like. The fine irregularities are not particularly limited, but include irregularities having clear structural units such as rectangular parallelepiped, cylindrical, elliptical cylinder, triangular prism, sphere, aspheric surface, etc., irregularities having a matte or hairline shape but not clear structural units, or combinations thereof, and irregularities having clear structural units but varying in shape, particularly size. As the shape of the irregularities, the height or recess of the shape can be 0.1 to 500 μm, and the pitch distance between the irregularities can be 10 to 1000 μm.

[0148] The surfaces of various molded articles using the methacrylic resin and the resin composition of this embodiment may be further subjected to surface functionalization treatments such as hard coat treatment, antiglare treatment, antireflection treatment, transparent conductive treatment, electromagnetic wave shielding treatment, and gas barrier treatment. There is no particular limitation on the thickness of these functional layers, but the thickness is usually in the range of 0.01 to 10 μm.

[0149] When the surface of a molded article is subjected to a hard coat treatment, the hard coat layer to be applied to the surface is formed, for example, by applying a coating liquid obtained by dissolving or dispersing an acrylate such as a silicone-based curable resin, an organic polymer composite inorganic fine particle-containing curable resin, a urethane acrylate, an epoxy acrylate, or a polyfunctional acrylate, and a photopolymerization initiator in an organic solvent, onto a film or sheet obtained from the methacrylic resin composition of the present embodiment by a conventionally known coating method, drying, and photocuring. In addition, before applying the hard coat layer, in order to improve adhesion, for example, a method of forming a hard coat layer after previously providing an easy-adhesion layer, a primer layer, an anchor layer, or the like containing inorganic fine particles in its composition can be used. The antiglare layer applied to the surface is formed by forming fine particles of silica, melamine resin, acrylic resin or the like into an ink, applying it onto the other functional layers by a conventionally known application method, and curing it with heat or light. Examples of the anti-reflection layer to be applied to the surface include thin films of inorganic materials such as metal oxides, fluorides, silicides, borides, nitrides, and sulfides; single or multiple layers of resins with different refractive indices such as acrylic resins and fluororesins; and laminated thin layers containing composite fine particles of inorganic compounds and organic compounds can also be used.

[0150] (Characteristics of Molded Product) The characteristics of the molded body of this embodiment will be described below.

[0151] In the molded body in this embodiment, the average absolute value of the in-plane retardation (Re) of the molded body is preferably 5.0 nm or less, more preferably 4.0 nm or less, even more preferably 3.0 nm or less, and even more preferably 1.5 nm or less, expressed as a value per mm of thickness. The standard deviation of the absolute value of the in-plane retardation (Re) of the molded article is preferably 2.0 nm or less, more preferably 1.5 nm or less, and further preferably 1.0 nm or less, expressed as a value per mm of thickness. The in-plane retardation of the molded article can be measured by the method described in the Examples below.

[0152] The thickness of the molded article of this embodiment is preferably 1.5 mm or less, more preferably 1.2 mm or less, and further preferably 1.0 mm or less.

[0153] (Use of Molded Body) The molded article made of the methacrylic resin composition of the present invention can be suitably used for applications such as optical parts in household products, OA equipment, AV equipment, battery electrical equipment parts, lighting equipment, and automobile parts. Examples of optical components in household products, office automation equipment, audiovisual equipment, battery-powered electrical equipment parts, lighting equipment, and the like include light guide plates, display front panels, and touch panels used in displays of smartphones, PDAs, tablet PCs, LCD televisions, and the like, as well as lenses for smartphones and tablet PC cameras, and optical lens components for head-mounted displays and LCD projectors, such as prism elements, waveguides, and lenses, particularly small, thin, irregularly shaped optical lenses, optical fibers, coating materials for optical fibers, lenses, Fresnel lenses, phase plates equipped with microlens arrays, and optical cover components. Examples of optical components in automobiles include light guide plates for in-vehicle displays; in-vehicle meter panels; optical components for head-up displays such as front panels, combiners, and optical cover parts for car navigation systems; in-vehicle camera lenses and light guide rods. In addition to the above, the present invention can also be preferably used as a camera focusing screen, or as a component for a digital signage display device that displays information on a thin display connected to a network for the purpose of publicity, advertising, etc., in places such as outdoors, in stores, public institutions, and transportation facilities. EXAMPLES

[0154] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0155] <1. Measurement of polymerization conversion rate> A part of the polymerization solution in each of the examples and comparative examples was collected, and the amount of monomer remaining in the polymerization solution sample was measured by dissolving the sample in chloroform to prepare a 5% by mass solution, adding n-decane as an internal standard substance, and measuring the concentration of the monomer remaining in the sample using gas chromatography (Shimadzu Corporation GC-2010) to determine the total mass (a) of the monomer remaining in the polymerization solution. The polymerization conversion rate (%) was calculated from the total mass (a) and the total mass (b) assumed to be the entire amount of the monomer added up to the time the sample was collected, using the formula (ba) / b×100.

[0156] <2. Analysis of structural units> In each example described below, unless otherwise specified, 1 H-NMR measurement and 13 The structural units of the produced methacrylic resin were identified by C-NMR measurement, and their amounts were calculated. 1 H-NMR measurement and 13 The measurement conditions for C-NMR measurement are as follows: Measurement equipment: Bruker DPX-400 Measurement solvent: CDCl3 or DMSO-d6 ·Measurement temperature: 40℃ When the ring structure of the methacrylic resin was a lactone ring structure, it was confirmed by the methods described in JP-A-2001-151814 and JP-A-2007-297620.

[0157] <3. Measurement of molecular weight and molecular weight distribution> The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resins produced in the examples and comparative examples described later were measured using the following apparatus and conditions. Measurement equipment: Tosoh Corporation, gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: 1 TSKguardcolumn SuperH-H, 2 TSKgel SuperHM-M, and 1 TSKgel SuperH2500 were connected in series. Column temperature: 40°C The developing solvent was tetrahydrofuran, the flow rate was 0.6 mL / min, and 0.1 g / L of 2,6-di-t-butyl-4-methylphenol (BHT) was added as an internal standard. Detector: RI (differential refractive index) detector, detection sensitivity: 3.0 mV / min Sample: 0.02 g of methacrylic resin or 20 mL of tetrahydrofuran solution of methacrylic resin. Injection volume: 10 μL Standard sample for calibration curve: The following ten types of polymethyl methacrylate (Polymer Laboratories; PMMA Calibration Kit MM-10) with known monodisperse weight peak molecular weights and different molecular weights were used. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methacrylic resin. Based on the calibration curve obtained by measuring the standard samples for the calibration curve, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin were determined.

[0158] <4. Glass transition temperature> The glass transition temperature (Tg) (°C) of the methacrylic resin was measured in accordance with JIS-K7121. First, from a sample that had been conditioned under standard conditions (23°C, 65% RH) (left at 23°C for one week), test pieces of approximately 10 mg each were cut out at four points (four locations). Next, a differential scanning calorimeter (PerkinElmer Japan Diamond DSC) was used under the condition of a nitrogen gas flow rate of 25 mL / min, where the sample was heated from room temperature (23°C) to 200°C (first heating) at 10°C / min, held at 200°C for 5 minutes to completely melt the sample, then cooled from 200°C to 40°C at 10°C / min, held at 40°C for 5 minutes, and heated again under the above heating conditions (second heating). The intersection (midpoint glass transition temperature) between the step-like change partial curve during the second heating and a straight line equidistant in the vertical direction from each baseline extension line was measured as the glass transition temperature (Tg) (°C). Four measurements were taken per sample, and the arithmetic average (rounded off to the nearest whole number) of the four measurements was taken as the measured value.

[0159] <5. Measurement of composition distribution of structural units> The methacrylic resins obtained in the examples and comparative examples were subjected to molecular weight fractionation using the following apparatus and conditions. ·Preparation device: LC-908 manufactured by Nippon Analytical Industry Co., Ltd. Fractionation conditions: Column: SHODEX K-2004 Eluent: chloroform, flow rate: 3 mL / min Detector: UV detector (254 nm) Sample: 3% by weight chloroform solution A 3 mL sample was injected, and fractions were collected at 1-minute intervals from elution time 18 to 43 minutes. The fractionation procedure was repeated three times, and fractions with the same elution time were pooled together. For each sample selected from the obtained fractions, the composition ratio of each structural unit was determined according to the above-mentioned <2. Analysis of structural units>. In addition, for each of the above samples, the molecular weight distribution of the methacrylic resin was measured according to the above-mentioned <3. Measurement of molecular weight and molecular weight distribution>, and the peak top molecular weight (Mp) was determined from the position of the apex of the peak of the molecular weight distribution curve.

[0160] <6. Measurement of orientation birefringence> The methacrylic resin obtained in each of the examples and comparative examples was first formed into a press film using a vacuum compression molding machine to prepare an unstretched sample. Specific sample preparation conditions were as follows: the methacrylic resin was placed in a 150 μm thick polyimide frame, sandwiched between two polyimide films and two iron plates, and set in a vacuum compression molding machine (Shinto Metal Industry Co., Ltd., SFV-30 model). It was preheated at 260°C under reduced pressure (approximately 10 kPa) for 10 minutes, then compressed at 260°C and approximately 10 MPa for 5 minutes. After releasing the reduced pressure and press pressure, it was transferred to a cooling compression molding machine and cooled to solidify. The obtained pressed film was aged for 24 hours or more in a constant temperature and humidity room adjusted to 23° C. and a humidity of 60%, and then used as an unstretched sample. The unstretched sample was cut into a thickness width of 40 mm and a length of 60 mm to prepare a test piece for measurement. A tensile test jig was set in a Shimadzu Autograph AG-5000D connected to a thermostatic bath (TCB-300S), and the sample was uniaxially free stretched with a chuck distance of 40 mm, a stretching temperature of Tg+20°C, and a stretching speed of 500 mm / min. The sample was then immediately taken out to room temperature to cool, and then aged for 24 hours in a constant temperature and humidity room adjusted to 23°C and 60% humidity to produce a stretched film. Several films were prepared at each of the stretch ratios of about 100% and 300%, and the orientation degree and orientation birefringence were measured by infrared dichroic ratio as described below, to find the orientation birefringence at orientation degrees of 0.03 and 0.08. The degree of orientation was measured using an infrared spectrometer Tensor 27 manufactured by Bruker Corp., and was determined by infrared dichroic ratio by a transmission method. Measurements are performed with a wavelength resolution of 2 cm -1 The stretched film was irradiated with infrared light polarized in the horizontal and vertical directions with respect to the stretching direction through a polarizing filter, and the absorbance was measured and calculated as A ∥ and A ⊥ It was decided. The infrared dichroic ratio D is expressed by the following formula. D=A ∥ / A ⊥ (c) If the angle between the direction of the vibration transition moment related to the absorption of the functional group of interest and the orientation direction or extension direction of the main chain is α, the degree of orientation f is expressed by the following formula.

number

[0161] <7. Photoelastic coefficient C R Measurements > The unstretched sample obtained in the above <6. Measurement of Orientation Birefringence> was cut into a film-like test piece with a width of 6 mm, and the photoelastic coefficient C was measured using a birefringence measuring device described in detail in Polymer Engineering and Science 1999, 39, 2349-2357. R (Pa -1 ) was measured. The film-like test piece was placed on a film tensioning device (manufactured by Imoto Manufacturing Co., Ltd.) similarly installed in a constant temperature and humidity chamber so that the distance between the chucks was 50 mm. Next, a birefringence measuring device (manufactured by Otsuka Electronics, RETS-100) was placed so that the optical path of the device was located at the center of the film, and the birefringence of the test piece was measured at a wavelength of 550 nm while applying a tensile stress with a distance between the chucks of 50 mm and a chuck movement speed of 0.1 mm / min. The birefringence (Δn) and tensile stress (σ R ) relationship, the slope of the line is calculated by least squares approximation, and the photoelastic coefficient (C R )(Pa -1 ) was calculated. For the calculation, the tensile stress was set to 2.5MPa or less. R Data between ≦10 MPa were used. C R=Δn / σ R Here, the birefringence (Δn) has the value shown below. Δn=nx-ny (nx: refractive index in the stretching direction, ny: refractive index in the in-plane direction perpendicular to the stretching direction)

[0162] <8. Measurement of phase difference in the in-plane direction of injection-molded pieces> The methacrylic resins obtained in Examples 1 to 7 and Comparative Examples 1 and 2 were injection molded using an injection molding machine (AUTO SHOT C Series MODEL 15A, manufactured by FANUC Corporation) in a flat mold having a fan gate and a size of 1 mm thick x 60 mm wide x 45 mm long as shown in FIG. FIG. 1(A) shows a plan view of the above-mentioned flat plate mold, and FIG. 1(B) shows a cross-sectional view of the flat plate mold in FIG. 1(A) taken along the line AA. First, the cylinder temperature was set to 270°C, the mold temperature to 90°C, the cooling time to 20 seconds, the injection screw speed to 50mm / s, and the holding pressure to 0kgf / cm. 2 By changing the injection pressure and performing injection molding, the minimum injection pressure (short shot point, SSP) at which the resin is completely filled in the mold was obtained. Next, the injection pressure was set to SSP + 50kgf / cm 2 A flat molded piece for measuring the in-plane retardation was obtained by injection molding under the setting of The obtained flat plate specimen was subjected to in-plane retardation distribution measurement at a wavelength of 520 nm using a PA-200-L manufactured by Photonic Lattice, Inc. The in-plane retardation distribution measurement was performed by observing an area of ​​55 mm width × 40 mm length (shaded area in Figure 1) in the center of the flat plate from above, and the average value and standard deviation of the absolute value of the in-plane retardation (Re) in the area were calculated and used as an index of evaluation.

[0163] <9. Color measurement of molded pieces> The methacrylic resins obtained in the examples and comparative examples were molded into rectangular test pieces having a thickness of 4 mm, a width of 10 mm, and a length of 80 mm using an injection molding machine (AUTO SHOT C Series MODEL 15A, manufactured by FANUC Corporation) at a molding temperature of 250°C and a mold temperature of 90°C. The mold was mirror-finished, and the end face on the short side had a slide core structure with no draft angle, resulting in a test piece that allowed color measurement using transmitted light with an optical path length of 80 mm in the long side direction. The YI of the obtained test piece was measured using a color difference meter (ASA-1, manufactured by Nippon Denshoku Industries Co., Ltd.) with a C light source and a 2° field of view and an optical path length of 80 mm.

[0164] <10. Color reproducibility of simulated light guide unit> The methacrylic resins obtained in the examples and comparative examples were injection-press molded using an injection molding machine with a clamping force of 50 tons under conditions of a molding temperature of 270°C and a mold temperature of 90°C to produce a light guide plate with a thickness of 0.6 mm, a width of 115 mm, and a length of 80 mm, with dots formed on the lower surface at a pitch of 100 to 300 μm. A light source was installed on the end surface on the long side, and a reflective sheet was further installed under the lower surface of the light guide plate to produce a simulated light guide unit in which light is emitted to the upper surface. Using a spectroradiometer, the chromaticity x and y of the emitted light at a position 5 mm from the end surface on the light source side and a position 75 mm from the end surface opposite to the end surface where the light source was installed were measured from the upper surface side, and the values ​​obtained by subtracting the value at the position 5 mm from the value at the position 75 mm were defined as Δx and Δy, respectively. It can be said that the smaller the values ​​of Δx and Δy, the smaller the color shift and the higher the color tone reproducibility.

[0165] [Raw materials] The raw materials used in the Production Examples and Comparative Production Examples described later are shown below. [[monomer]] Methyl methacrylate: Asahi Kasei Corporation N-Phenylmaleimide (phMI): Nippon Shokubai Co., Ltd. N-Cyclohexylmaleimide (chMI): Nippon Shokubai Co., Ltd. [[Polymerization initiator]] 1,1-Di(t-butylperoxy)cyclohexane: NOF Corporation's "Perhexa C" [[Chain transfer agent]] n-Octyl mercaptan: Kao Corporation [[Antioxidants]] Pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]: BASF "Irganox 1010" Tris(2,4-di-t-butylphenyl)phosphite: BASF "Irgafos168"

[0166] [Example 1] 358.6 kg of methyl methacrylate (hereinafter referred to as MMA), 29.4 kg of N-phenylmaleimide (hereinafter referred to as phMI), 67.7 kg of N-cyclohexylmaleimide (hereinafter referred to as chMI), 0.77 kg of n-octyl mercaptan as a chain transfer agent, and 224.3 kg of meta-xylene (hereinafter referred to as mXy) ​​were weighed out and placed in a 1.25m 3 The mixture was added to a reactor and stirred to obtain a mixed monomer solution. Next, 88.0 kg of MMA, 6.3 kg of phMI, and 142.4 kg of mXy were weighed and added to Tank 1 with stirring to obtain a mixed monomer solution for additional addition. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and the liquid in Tank 1 was bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the solution temperature in the reactor to 115°C, and polymerization was initiated by adding a polymerization initiator solution prepared by dissolving 0.470 kg of 1,1-di(t-butylperoxy)cyclohexane in 1.905 kg of mXy at a rate of 1.0 kg / hour while stirring at 50 rpm. During the polymerization, the solution temperature in the reactor was controlled at 115±2° C. by adjusting the temperature with a jacket. After 30 minutes from the start of the polymerization, the addition rate of the initiator solution was reduced to 0.5 kg / hour. In addition, starting from 1 hour after the start of polymerization, the additional mixed monomer solution was added in its entirety from Tank 1 at a constant rate over a period of 4 hours. Furthermore, the addition rate of the initiator solution was reduced to 0.25 kg / hour 3.5 hours after the start of polymerization, and the addition was stopped 5 hours after the start of polymerization. After 12 hours had elapsed since the start of the polymerization, a polymer solution containing a methacrylic resin having a ring structure in the main chain was obtained, and the polymerization was terminated. The polymer solution was sampled 2 hours and 12 hours after the start of polymerization, and the polymerization conversion was analyzed from the remaining monomer concentration. The polymerization conversion after 2 hours was MMA 78.9%, phMI 77.3%, and chMI 70.4%, and the polymerization conversion after 12 hours was MMA 97.9%, phMI 99.4%, and chMI 99.2%. Taking into account the monomers added after 2 hours from the start of polymerization, the polymerization conversion after 2 hours was converted as the consumption rate of each monomer added by the end of polymerization, and was MMA 67.2%, phMI 67.1%, and chMI 70.4%. The polymer solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer, both of which had been preheated to 250°C, to carry out devolatilization. The degree of vacuum in the vaporizer was set to 10-15 Torr. The resin that flowed down the vaporizer was pumped out by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin. The composition of the obtained pellet-like polymer was confirmed to be 81.0 mass%, 6.6 mass%, and 12.4 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively, and the weight-average molecular weight was 108,000 and Mw / Mn was 2.04. Other physical properties are shown in Table 1.

[0167] [Example 2] A methacrylic resin was obtained in the same manner as in Example 1, except that the amount of MMA added to the reactor was changed to 357.0 kg, the amount of phMI to 30.1 kg, and the amount of chMI to 68.9 kg, and the amount of MMA added to tank 1 was changed to 87.6 kg and the amount of phMI to 6.4 kg. The obtained physical properties are shown in Table 1.

[0168] [Example 3] The amount of MMA, phMI, and chMI added to the reactor were changed to 355.4 kg, 30.8 kg, and 70.1 kg, respectively, the amount of MMA and phMI added to tank 1 were changed to 87.2 kg and 6.5 kg, respectively, and further, 0.550 kg of Irganox1010 and 0.825 kg of Irgafos168 were added as antioxidants before devolatilization, and a methacrylic resin was obtained in the same manner as in Example 1. The obtained physical properties are shown in Table 1.

[0169] [Example 4] The amount of MMA, phMI, and chMI added to the reactor were changed to 353.8 kg, 31.5 kg, and 70.3 kg, respectively, the amount of MMA and phMI added to tank 1 were changed to 86.8 kg and 6.6 kg, respectively, and further, 0.550 kg of Irganox1010 and 0.825 kg of Irgafos168 were added as antioxidants before devolatilization, and a methacrylic resin was obtained in the same manner as in Example 1. The obtained physical properties are shown in Table 1.

[0170] [Example 5] A methacrylic resin was obtained in the same manner as in Example 2, except that the amount of n-octyl mercaptan added to the reactor was changed to 0.41 kg. The physical properties obtained are shown in Table 1.

[0171] [Example 6] A methacrylic resin was obtained in the same manner as in Example 1, except that the amount of pHMI added to the reactor was changed to 28.2 kg and the amount of pHMI added to tank 1 was changed to 7.5 kg. The polymer solution was sampled 2 hours and 12 hours after the start of polymerization, and the polymerization conversion was analyzed from the remaining monomer concentration. The polymerization conversion after 2 hours was MMA 79.0%, phMI 77.0%, and chMI 70.6%, and the polymerization conversion after 12 hours was MMA 97.8%, phMI 99.3%, and chMI 99.1%. Taking into account the monomers added after 2 hours from the start of polymerization, the polymerization conversion after 2 hours was converted as the consumption rate of each monomer added by the end of polymerization, and was MMA 67.3%, phMI 64.9%, and chMI 70.6%. Other physical properties are shown in Table 1.

[0172] [Example 7] A methacrylic resin was obtained in the same manner as in Example 1, except that the amount of pHMI added to the reactor was changed to 27.2 kg and the amount of pHMI added to tank 1 was changed to 8.5 kg. The polymer solution was sampled 2 hours and 12 hours after the start of polymerization, and the polymerization conversion was analyzed from the remaining monomer concentration. The polymerization conversion after 2 hours was MMA 78.8%, phMI 77.2%, and chMI 70.7%, and the polymerization conversion after 12 hours was MMA 97.9%, phMI 99.3%, and chMI 99.2%. Taking into account the monomers added after 2 hours from the start of polymerization, the polymerization conversion after 2 hours was converted as the consumption rate of each monomer added by the end of polymerization, and was MMA 67.2%, phMI 63.4%, and chMI 70.7%. Other physical properties are shown in Table 1.

[0173] [Example 8] In a reactor equipped with a jacket temperature control device and a stirring blade, 40 parts by mass of MMA, 60 parts by mass of mXy, and 0.08 parts by mass of n-octyl mercaptan, a chain transfer agent, were charged, and nitrogen bubbling was performed for 1 hour to remove dissolved oxygen. Then, steam was blown into the jacket to raise the solution temperature in the reactor to 120 ° C., and while stirring at 50 rpm, a polymerization initiator solution in which 0.02 parts by mass of 1,1-di(t-butylperoxy)cyclohexane was dissolved in 0.10 parts by mass of mXy was added at a constant speed for 5 hours to polymerize, and the mixture was further aged at 120 ° C. for 3 hours, and the polymerization was terminated 8 hours after the start of polymerization to obtain a PMMA mXy solution. After the polymerization was completed, the liquid temperature was lowered to 50 ° C. Next, a mixed solution consisting of 12 parts by mass of monomethylamine and 12 parts by mass of methanol was dropped into the reactor at room temperature, and the liquid temperature was raised to 170°C and stirred under pressure for 1 hour to allow the glutarimide cyclization reaction to proceed. The liquid temperature was lowered to 120°C, and the inside of the reactor was reduced in pressure to distill off unreacted monomethylamine and methanol, as well as a portion of mXy, to obtain a glutarimide-cyclized methacrylic polymer solution containing about 50% by mass of mXy. The polymer solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer, both of which had been preheated to 250°C, to carry out devolatilization. The degree of vacuum in the vaporizer was set to 10-15 Torr. The resin that flowed down the vaporizer was pumped out by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin. The composition of the obtained methacrylic resin composition was confirmed to be 5.2% by mass of glutarimide structural units, and the weight average molecular weight was 93,000 and Mw / Mn was 1.79. Other physical properties are shown in Table 1.

[0174] [Comparative Example 1] 440.0 kg of MMA, 37.0 kg of pHMI, 73.0 kg of CHMI, 1.12 kg of n-octyl mercaptan as a chain transfer agent, and 450 kg of mXy were weighed out and placed in a 1.25m 3 The mixture was added to a reactor and stirred to obtain a mixed monomer solution. Nitrogen was bubbled into the solution in the reactor at a rate of 30 L / min for 1 hour to remove dissolved oxygen. Then, steam was blown into the jacket to raise the solution temperature in the reactor to 125°C, and polymerization was started by adding a polymerization initiator solution in which 0.231 kg of 1,1-di(t-butylperoxy)cyclohexane was dissolved in 5.769 kg of mXy at a rate of 1 kg / hour for 6 hours while stirring at 50 rpm. During the polymerization, the solution temperature in the reactor was controlled at 125±2°C by adjusting the temperature with a jacket. After 8 hours had passed since the start of polymerization, a polymerization solution containing a methacrylic resin having a ring structure in the main chain was obtained. Sampling of the polymer solution was performed 2.5 hours, 4 hours, and 8 hours (at the end of polymerization) after the start of polymerization, and the polymerization conversion rate was analyzed from the remaining monomer concentration. The polymerization conversion rate after 2.5 hours was 68.2% MMA, 66.1% phMI, and 54.1% chMI, the polymerization conversion rate after 4 hours was 83.8% MMA, 81.5% phMI, and 71.3% chMI, and the polymerization conversion rate after 8 hours was 95.9% MMA, 96.8% phMI, and 93.3% chMI. The polymer solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer, both of which had been preheated to 250°C, to carry out devolatilization. The degree of vacuum in the vaporizer was set to 10-15 Torr. The resin that flowed down the vaporizer was pumped out by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin. The composition of the obtained pellet-like polymer was confirmed to be 80.2 mass%, 6.8 mass%, and 13.0 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively, and the weight-average molecular weight was 131,000 and Mw / Mn was 2.26. Other physical properties are shown in Table 1.

[0175] [Comparative Example 2] 335.5 kg of MMA, 37.4 kg of pHMI, 67.1 kg of CHMI, 0.30 kg of n-octyl mercaptan as a chain transfer agent, and 236.9 kg of mXy were weighed out and placed in a 1.25m flask equipped with a jacket temperature control device and a stirring blade. 3 The mixture was added to a reactor and stirred to obtain a mixed monomer solution. Next, 123.1 kg of mXy was weighed out and added to Tank 1 as a solvent. Furthermore, 110.0 kg of MMA and 90.0 kg of mXy were weighed into Tank 2 and stirred to obtain an MMA solution for further addition. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and the liquid in tanks 1 and 2 was bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the solution temperature in the reactor to 123°C, and while stirring at 50 rpm, a polymerization initiator solution prepared by dissolving 0.481 kg of 1,1-di(t-butylperoxy)cyclohexane in 2.644 kg of mXy was added at a rate of 1.0 kg / hour to initiate polymerization. During the polymerization, the solution temperature in the reactor was controlled at 123±2°C by adjusting the temperature with the jacket. Thirty minutes after the start of polymerization, the addition rate of the initiator solution was reduced to 0.25 kg / hour. Furthermore, from 30 minutes after the start of polymerization, the entire amount of additional solvent was added from Tank 1 at a constant rate over a period of 3.5 hours. Then, 4 hours after the initiation of polymerization, the addition rate of the initiator solution was increased to 0.75 kg / hour, and the additional MMA solution was added in its entirety from Tank 2 at a constant rate over a period of 2 hours. Further, 6 hours after the start of polymerization, the addition rate of the initiator solution was reduced to 0.25 kg / hour, and 7 hours after the start of polymerization, the addition was stopped. After 8 hours had elapsed since the start of the polymerization, a polymer solution containing a methacrylic resin was obtained, and the polymerization was terminated. The polymer solution was sampled 2.5 hours and 8 hours after the start of polymerization, and the polymerization conversion was analyzed from the remaining monomer concentration. The polymerization conversion after 2.5 hours was MMA 83.5%, phMI 80.1%, and chMI 71.9%, and the polymerization conversion after 8 hours was MMA 92.0%, phMI 99.1%, and chMI 97.8%. Taking into account the monomers added after 2.5 hours from the start of polymerization, the polymerization conversion after 2.5 hours was converted as the consumption rate of each monomer added by the end of polymerization, and was MMA 62.9%, phMI 80.1%, and chMI 71.9%. The polymer solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer, both of which had been preheated to 250°C, to carry out devolatilization. The degree of vacuum in the vaporizer was set to 10-15 Torr. The resin that flowed down the vaporizer was pumped out by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin. The composition of the obtained pellet-like polymer was confirmed to be 80.0 mass %, 7.2 mass %, and 12.8 mass % of structural units derived from MMA, phMI, and chMI monomers, respectively, and the weight-average molecular weight was 137,000 and Mw / Mn was 2.32. Other physical properties are shown in Table 1.

[0176] [Comparative Example 3] 141.2 kg of MMA, 14.6 kg of phMI, 27.5 kg of chMI, 0.174 kg of n-octyl mercaptan as a chain transfer agent, and 147.0 kg of mXy were weighed out and placed in a 1.25m 3 The mixture was added to a reactor and stirred to obtain a mixed monomer solution. Next, 262.3 kg of MMA, 27.1 kg of phMI, 51.1 kg of chMI, and 273.0 kg of mXy were weighed and added to Tank 1 with stirring to obtain a mixed monomer solution for additional addition. In addition, 56.1 kg of MMA was weighed into Tank 2. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and tank 1 and tank 2 were each bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the solution temperature in the reactor to 124°C, and polymerization was initiated by adding a polymerization initiator solution prepared by dissolving 0.348 kg of 1,1-di(t-butylperoxy)cyclohexane in 4.652 kg of mXy at a rate of 2 kg / hour while stirring at 50 rpm. During the polymerization, the solution temperature in the reactor was controlled at 124±2° C. by adjusting the temperature with the jacket. 30 minutes after the start of the polymerization, the addition rate of the initiator solution was reduced to 1 kg / hour, and further, 306.8 kg / hour of the additional mixed monomer solution was added from Tank 1 for 2 hours. Then, 2 hours and 45 minutes after the initiation of polymerization, MMA was added in its entirety from Tank 2 at a rate of 112.1 kg / hour over a period of 30 minutes. Furthermore, the addition rate of the initiator solution was reduced to 0.5 kg / hour 3.5 hours after the start of polymerization, to 0.25 kg / hour 4.5 hours after, and to 0.125 kg / hour 6 hours after, and addition was stopped 7 hours after the start of polymerization. After 10 hours had passed since the start of polymerization, a polymerization solution containing a methacrylic resin having a ring structure in the main chain was obtained. The polymer solution was sampled 3.25 hours and 10 hours after the start of polymerization, and the polymerization conversion was analyzed from the remaining monomer concentration. The polymerization conversion after 3.25 hours was 69.5% for MMA, 68.9% for phMI, and 63.1% for chMI, and after 10 hours it was 96.6% for MMA, 96.0% for phMI, and 91.8% for chMI. Taking into account the monomers added after 2 hours from the start of polymerization, the polymerization conversion after 2 hours was converted as the consumption rate of each monomer added by the end of polymerization, and was 69.5% for MMA, 68.9% for phMI, and 63.1% for chMI. The polymer solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer, both of which had been preheated to 250°C, to carry out devolatilization. The degree of vacuum in the vaporizer was set to 10-15 Torr. The resin that flowed down the vaporizer was pumped out by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin. The composition of the obtained pellet-like polymer was confirmed to be 79.8 mass%, 7.2 mass%, and 13.0 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively, and the weight-average molecular weight was 141,000 and Mw / Mn was 1.96. Other physical properties are shown in Table 1.

[0177] [Comparative Example 4] Poly(methyl methacrylate) was imidized with monomethylamine using a co-rotating twin-screw extruder to obtain a methacrylic resin composition having a glutarimide structure. A 40mm screw diameter co-rotating twin screw extruder was used, the extruder cylinder temperature was set to 270°C, the screw rotation speed was set to 150 rpm, and polymethyl methacrylate with Mw of 108,000 was fed from the hopper at 20 kg / hour, while nitrogen was flowed into the extruder at a flow rate of 200 mL / min. After the resin was melted and filled by the kneading block, 1.8 parts by mass of monomethylamine was injected from the nozzle relative to the raw resin to carry out the imidization reaction. A reverse flight was placed at the end of the reaction zone (before the vent port) to fill the zone with resin. The by-products and excess methylamine after the reaction were removed by reducing the pressure at the vent port to 50 Torr. The resin that came out as strands from the die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain an imide resin. Next, a 40mm screw diameter co-rotating twin screw extruder was used, the extruder cylinder temperature was set to 250°C, and the screw rotation speed was set to 150 rpm. The obtained imide resin was fed at 20 kg / hr, and the resin was melted and filled by a kneading block, and then a mixed solution of dimethyl carbonate and triethylamine was injected from a nozzle as an esterification agent to reduce the carboxylic acid group in the resin. Dimethyl carbonate was 3.2 parts by mass and triethylamine was 0.8 parts by mass per 100 parts by mass of imide resin. A reverse flight was placed at the end of the reaction zone to fill the resin. The by-products after the reaction and excess dimethyl carbonate were removed by reducing the pressure at the vent port to 50 Torr. The resin that came out as strands from the die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain a methacrylic resin composition having a glutarimide structure. The composition of the obtained methacrylic resin composition was confirmed to be 5.2% by mass of glutarimide structural units, and the weight average molecular weight was 102,000 and Mw / Mn was 1.76. Other physical properties are shown in Table 1.

[0178] [Table 1-1] [Table 1-2] [Table 1-3]

[0179] As is clear from the Examples and Comparative Examples, in a methacrylic resin having a ring structure unit derived from an N-substituted maleimide monomer, when the consumption rate of methyl methacrylate is taken as the consumption rate relative to the total amount of each monomer added by the end of polymerization, in an Example in which additional monomers were added and polymerized so that the difference in consumption rate with N-phenylmaleimide and N-cyclohexylmaleimide becomes small at a point in time when the consumption rate of methyl methacrylate is 60 to 70%, the composition distribution of the structural unit having a ring structure is small, and when the composition is adjusted so that the orientation birefringence at an orientation degree of 0.03 is positive, there exists a composition range in which the orientation birefringence at an orientation degree of 0.08 is negative, and when this resin is injection molded, a molded product with low birefringence is obtained. On the other hand, in the comparative examples in which the consumption rate difference between methyl methacrylate and N-phenylmaleimide and N-cyclohexylmaleimide is large at a point in time when the consumption rate of methyl methacrylate is 60 to 70%, the composition distribution of structural units having ring structures is large, and it is not possible to adjust the composition so that the signs of the orientation birefringence at an orientation degree of 0.03 and an orientation degree of 0.08 are different, and the birefringence of the molded body cannot be sufficiently reduced. Furthermore, in the case of methacrylic resins having glutarimide structural units, a polymer with a uniform composition distribution of ring structures can be obtained by carrying out a cyclization reaction in a solution state, and compositions exist in which the signs of orientation birefringence differ at an orientation degree of 0.03 and an orientation degree of 0.08, making it possible to obtain molded articles with low birefringence.

[0180] [Example 9] Both sides of the injection molded plate obtained in Example 1 were spray-coated with Acier E50PG manufactured by Nidek Co., Ltd., and after drying, were irradiated with approximately 1000 mJ / cm 2 using a high-pressure mercury lamp. 2 The coated film was irradiated with ultraviolet light of about 1000 ohms to form a hard coat layer having a thickness of about 3 μm. Furthermore, an anti-reflection layer was formed by vacuum deposition of TiO2 (film thickness 13 nm), SiO2 (film thickness 36 nm), TiO2 (film thickness 119 nm), and SiO2 (film thickness 88 nm) in that order.

[0181] The injection-molded plate obtained in Example 1 had a total light transmittance of 92.5%, whereas the injection-molded plate having the hard coat layer and the antireflection layer formed thereon had a good total light transmittance of 97.5%. Furthermore, when a cross-cut test was carried out in accordance with JIS K5600-5-6, no peeling of the hard coat layer was observed. Next, the injection-molded plate having the hard coat layer and the anti-reflection layer formed thereon was placed in a thermo-hygrostat chamber at a temperature of 85°C and a relative humidity of 85% for 500 hours, after which the total light transmittance was measured and a cross-cut test was carried out in the same manner, but no changes were observed compared to before the plate was placed in the thermo-hygrostat chamber. [Industrial Applicability]

[0182] The methacrylic resin of the present embodiment has high heat resistance, and when the methacrylic resin or a composition thereof is injection molded, the birefringence is highly controlled. The methacrylic resin molded article of the present invention can be used as an optical member in household appliances, office automation equipment, audiovisual equipment, battery-powered electrical equipment parts, lighting equipment, etc. Examples of the optical components include light guide plates, display front panels, and touch panels used in displays of smartphones, PDAs, tablet PCs, liquid crystal televisions, and the like, as well as lenses for smartphones and tablet PC cameras, and optical lens components for head-mounted displays and liquid crystal projectors, such as prism elements, waveguides, and lenses, particularly small, thin, irregularly shaped optical lenses, optical fibers, coating materials for optical fibers, lenses, Fresnel lenses, phase plates equipped with microlens arrays, and optical cover components. Examples of optical components in automobiles include light guide plates for in-vehicle displays; in-vehicle meter panels; optical components for head-up displays such as front panels, combiners, and optical cover parts for car navigation systems; in-vehicle camera lenses and light guide rods. In addition to the above, the present invention can also be preferably used as a camera focusing screen, or as a component for a digital signage display device that displays information on a thin display connected to a network for the purpose of publicity, advertising, etc., in places such as outdoors, in stores, public institutions, and transportation facilities.

Claims

1. An injection-molded article having a fine unevenness on its surface, the article being obtained using a composition containing a methacrylic resin containing a structural unit having a ring structure in its main chain, Regarding the shape of the fine irregularities, the height or concave portion is 0.1 to 500 μm, and the pitch distance between the irregularities is 10 to 1000 μm, The methacrylic resin is The glass transition temperature is more than 120° C. and not more than 160° C. the difference in the abundance ratio of structural units having a ring structure in the main chain between a fraction having a peak top molecular weight of 40,000 to 50,000 and a fraction having a peak top molecular weight of 240,000 to 260,000 obtained by molecular weight fractionation is 3.0% by mass or less; Contains structural units derived from N-substituted maleimide monomers and / or glutarimide structural units, The sign of orientation birefringence for a first orientation degree is different from the sign of orientation birefringence for a second orientation degree having a value higher than the first orientation degree, The first orientation degree is 0.03, and the second orientation degree is 0.

08. An injection molded article,

2. The absolute value of the difference between the absolute value of the orientation birefringence when the methacrylic resin is oriented so that the orientation degree is 0.03 and the absolute value of the orientation birefringence when the methacrylic resin is oriented so that the orientation degree is 0.08 is 5.0 × 10 -5 2. The injection molded body according to claim 1, wherein:

3. The absolute value of the orientation birefringence when the methacrylic resin is oriented so as to have an orientation degree of 0.03 is 0.1×10 -5 Above 5.0 x 10 -5 When the orientation degree is 0.08, the absolute value of the orientation birefringence is 8.0×10 -5 3. The injection molded body according to claim 2, wherein:

4. 4. The injection molded article according to claim 1, wherein a molded piece obtained by injection molding the methacrylic resin has a yellowness index (YI) of 20 or less, measured at an optical path length of 80 mm.

5. The photoelastic coefficient of the methacrylic resin is −3×10 -12 ~ +3 x 10 -12 P -1 The injection molded article according to any one of claims 1 to 4,

6. The methacrylic resin has an average absolute value of an in-plane retardation (Re) measured at a wavelength of 520 nm in a region having a width of 55 mm and a length of 40 mm at the center of the plate when the methacrylic resin is injection molded into a plate shape having a thickness of 1 mm, a width of 60 mm, and a length of 45 mm, of 3.5 nm or less. The injection molded article according to any one of claims 1 to 5.

7. An optical component or an automobile component, comprising the injection molded article according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • High-strength, heat-resistant film or sheet

    JP1994240017A

  • Heat-resistant methacrylic resin and its preparation

    JP1997324016A

  • Non-birefringent optical plastic material and optical member

    JP2006308682A

  • Imide resin, resin composition for optical use, using the same, and molded article

    JP2006328330A

  • Resin composition for optical material, and optical element

    JP2008015199A